Battery, electric device
Patent Information
- Application Number
- CN202611329233.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]鉴于上述问题,本申请提供一种钠离子层状氧化物正极材料、正极极片、电池、用电装置,能够改善镍铁锰基层状氧化物水稳定性差的问题
[0028]本申请实施例公开的电池可以用于以电池作为电源的用电装置,或者以电池作为储能元件的各种储能系统,用于提供电能。上述电池的正极极片包含具有优异水稳定性的钠离子层状氧化物正极材料,可以改善电池的循环稳定性等电化学性能。因此,采用上述电池能够稳定地为各种用电装置提供电能,改善各种用电装置的使用体验。
Smart Images

Figure CN122992053A_ABST
Abstract
Description
[0001] This application is a divisional application of the invention patent application with application number 202311399969.6, application date October 26, 2023, entitled "Sodium ion layered oxide cathode material, cathode sheet, battery, and electrical device". Technical Field
[0002] This application belongs to the field of battery technology, and in particular relates to sodium ion layered oxide cathode materials, cathode sheets, batteries, and electrical devices. Background Technology
[0003] Sodium-ion batteries have attracted widespread attention and research because their raw materials are abundant and widely distributed in nature.
[0004] Cathode materials are crucial for achieving the high capacity, high voltage, and long cycle life of sodium-ion batteries. Currently, the most researched materials for sodium-ion batteries include layered oxides, polyanionic oxides, and Prussian blue analogues. Among these, nickel-iron-manganese layered oxides have become a research hotspot due to their higher specific capacity, superior performance, and simple synthesis compared to other cathode materials. However, these layered oxides suffer from poor water stability, which hinders the development of sodium-ion batteries. Summary of the Invention
[0005] In view of the above problems, this application provides a sodium ion layered oxide cathode material, cathode sheet, battery, and power device, which can improve the problem of poor water stability of nickel-iron-manganese layered oxides.
[0006] In a first aspect, this application provides a sodium-ion layered oxide cathode material, comprising Na x Ni a Fe b Mn c M 1 d M 2 e O 2-p A p , where 0.6 < x <1.2, 0≤a, 0≤b, 0≤c, 0≤d, 0<e≤0.15, a+b+c+d+e=1, 0<(a+b) / (c+d+e)≤19, 0≤ p ≤0.1; the M 1 Includes one or more elements from groups IA to VA and groups IB to VIIB, wherein M 2 It includes one or more elements selected from Ga, Ta, and Zr, wherein A includes one or more nonmetallic elements from groups VIA and VIIA.
[0007] This application involves doping a sodium-ion layered oxide cathode material containing Ni and Fe with one or more elements selected from Ga, Ta, and Zr (M). 2 ), part M 2 Elements occupy the surface positions of Ni and Fe in the sodium ion layered oxide cathode material, thus reducing the amount of Ni and Fe on the surface of the sodium ion layered oxide cathode material. These M elements... 2 The element itself is highly stable and does not readily coordinate with oxygen in water; therefore, M 2 Doping with elements can reduce the number of elements in sodium ion layered oxide cathode materials that can coordinate with oxygen contained in water, thereby improving the water stability of the material.
[0008] At the same time, in combination with Mn, M 1 By adjusting the proportions of each element, the thermodynamic energy of the reaction between sodium ion layered oxide cathode material and water increases, which means that the reaction between sodium ion layered oxide cathode material and water becomes more difficult, thereby enhancing the structural stability of sodium ion layered oxide cathode material and further improving its water stability.
[0009] In some embodiments, the M 1 Includes one or more of Cu, Li, Ti, K, Nb, Mg, Ca, Mo, Zn, Cr, W, Bi, Sn, Ge, Al, Si, P, and B. These metallic elements, or nonmetallic elements and half-metallic elements, are combined with M. 2 Co-doping with Ni and Fe increases the thermodynamic energy of the reaction between the sodium ion layered oxide cathode material and water, which helps to suppress the reaction between the sodium ion layered oxide cathode material and water and enhances the water stability of the sodium ion layered oxide cathode material.
[0010] In some embodiments, A includes one or more of F, Cl, and S. Doping oxygen sites in sodium ion layered oxide cathode materials with element A helps reduce oxygen defects in the crystal lattice and improves the structural stability of the sodium ion layered oxide cathode material.
[0011] In some embodiments, 0.01 ≤ e ≤ 0.15, and optionally, 0.1 ≤ e ≤ 0.15. e represents the atomic percentage of Ga, Ta, and Zr doping elements in the sodium-ion layered oxide cathode material, and also reflects the doping amount. With appropriate Ga, Ta, and Zr doping amounts, the water stability of the sodium-ion layered oxide cathode material can be effectively improved, while having minimal negative impact on its capacity.
[0012] In some embodiments, 0 < (a+b) / (c+d+e) ≤ 1.8, and optionally, 0 < (a+b) / (c+d+e) ≤ 1. (a+b) / (c+d+e) reflects the relationship between Ni and Fe in the sodium-ion layered oxide cathode material and Mn and Mn. 1 M 2 The ratios among the three, and under these ratios, Mn, M 1 M 2 It can effectively suppress the reaction between Ni and Fe and water, and enhance the water stability of sodium ion layered oxide cathode materials.
[0013] In some embodiments, 0 ≤ a ≤ 0.45, and optionally, 0 ≤ a ≤ 0.4. 'a' reflects the atomic percentage of Ni in the sodium-ion layered oxide cathode material. At a certain Ni content, it helps to improve the specific capacity of the sodium-ion layered oxide cathode material, especially its specific capacity at high voltages. Meanwhile, in the sodium-ion layered oxide cathode material of this application embodiment, due to the interaction of one or more elements among Ga, Ta, and Zr with Mn and Mn... 1 Together, they can suppress the reaction of Ni with water to form nickel oxide, as well as the side reaction with the electrolyte during electrochemical processes to form nickel oxide, thus exhibiting excellent water stability.
[0014] In some embodiments, 0 ≤ b ≤ 0.5, and optionally, 0.19 ≤ b ≤ 0.39. b reflects the atomic percentage of Fe in the sodium-ion layered oxide cathode material. At a certain Fe content, it helps to improve the specific capacity of the sodium-ion layered oxide cathode material, especially its specific capacity under high voltage. Meanwhile, in the sodium-ion layered oxide cathode material of this application embodiment, one or more elements selected from Ga, Ta, and Zr are combined with Mn and Mn... 1 Together, they can suppress the reaction of Fe with water to form iron oxides, as well as the side reaction with the electrolyte during electrochemical processes to form iron oxides, thus exhibiting excellent water stability.
[0015] In some embodiments, 0 ≤ c ≤ 0.5. c can reflect the atomic percentage of Mn in the sodium-ion layered oxide cathode material. Under a suitable atomic percentage, Mn can react with Ga, Ta, Zr, and Mn. 1 The elements work together to improve the water stability of sodium ion layered oxide cathode materials. Meanwhile, Mn has a significant impact on improving the capacity of sodium ion layered oxide cathode materials.
[0016] In some embodiments, 0 ≤ d ≤ 0.2, and optionally, 0 ≤ d ≤ 0.1. d can reflect M. 1 In sodium-ion layered oxide cathode materials, the atomic percentage, under a suitable atomic percentage, is M1 It can work with Ga, Ta, Zr and Mn to improve the water stability of sodium ion layered oxide cathode materials.
[0017] In some embodiments, the M 2 Including Ga, the proportions of each element in the sodium ion layered oxide cathode material are as follows: 0.7≤ x ≤1, 0≤a≤0.39, 0<b, 0<c, 0≤d, 0<e≤0.15, a+b+c+d+e=1; 0<(a+b) / (c+d+e)≤1.8; or, The M 2 Including Ta, the proportions of each element in the sodium ion layered oxide cathode material are as follows: 0.6 < x <1.2, 0≤a, 0≤b, 0≤c≤0.5, 0≤d, 0<e≤0.15, a+b+c+d+e=1; 0<(a+b) / (c+d+e)≤19; or, The M 2 Including Zr, the proportions of each element in the sodium ion layered oxide cathode material are as follows: 0.7≤ x ≤1, 0≤a≤0.39, 0<b, 0<c, 0≤d, 0<e≤0.15, a+b+c+d+e=1; 0<(a+b) / (c+d+e)≤1.8.
[0018] Ga, Ta, Zr three kinds of M 2 Doping with any of the three elements can improve the structure of sodium-ion layered oxide cathode materials, thereby enhancing their water stability. However, the effects of the three elements on improving the water stability of sodium-ion layered oxide cathode materials also vary. When using different M... 2 In this case, by adaptively adjusting and optimizing the proportions of various elements in the sodium ion layered oxide cathode material, it is possible to fully utilize the different M... 2 It enhances water stability.
[0019] In some embodiments, the sodium-ion layered oxide cathode material includes NaNi. 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Ga 0.01 O2, NaNi 0.2 Fe 0.2 Mn 0.4 Cu 0.05 Ga 0.15 O2, NaNi 0.2 Fe 0.3 Mn0.4 Cu 0.09 Ga 0.01 O2、NaNi 0.2 Feb 0.29 Mr 0.4 Zn 0.1 Ga 0.01 O2、NaNi 0.2 Feb 0.3 0Mn 0.4 Mg 0.05 Ga 0.0 5O2、NaNi 0.1 Feb 0.39 Mr 0.4 Cu 0.1 Ga 0.01 O2、NaFe 0.39 Mr 0.5 Cu 0.1 Ga 0.01 O2、NaNi 0.39 Feb 0.2 Mr 0.4 Ga 0.01 O2、NaNi 0.25 Feb 0.39 Mr 0.3 Cu 0.05 Ga 0.01 O2、Na 0.7 Ni 0.2 Feb 0.29 Mr 0.4 Cu 0.1 Ga 0.01 O2、NaNi 0.2 Feb 0.29 Mr 0.4 Cu 0.1 Dad 0.01 O2、NaNi 0.2 Feb 0.2 Mr 0.4 Cu 0.05 Dad 0.15 O2、NaNi 0.3 Feb 0.3 Mr 0.4 Cu 0.09 Dad 0.01 O2、NaNi 0.2 Feb 0.29 Mr 0.4 Zn 0.1 Dad 0.01 O2、NaNi 0.2 Feb 0.30 Mr 0.4 Mg 0.05 Dad 0.0 5O2、NaNi0.3 Fe 0.19 Mn 0.4 The 0.1 Ta 0.01 O2、NaNi 0.1 Fe 0.39 Mn 0.4 The 0.1 Ta 0.01 O2、NaFe 0.39 Mn 0.5 The 0.1 Ta 0.01 O2、NaNi 0.39 Mn 0.5 Zn 0.1 Ta 0.01 O2、NaNi 0.45 Fe 0.5 The 0.04 Ta 0.01 O2、NaNi 0.39 Fe 0.2 Mn 0.4 Ta 0.01 O2、Na 1.03 Aunt 0.2 Fe 0.29 Mn 0.4 The 0.1 Ta 0.01 O2、Na 0.7 Aunt 0.2 Fe 0.29 Mn 0.4 The 0.1 Ta 0.01 O2、NaNi 0.25 Fe 0.39 Mn 0.3 The 0.05 Ta 0.01 O2、NaNi 0.2 Fe 0.29 Mn 0.4 The 0.1 Zr 0.01 O2、NaNi 0.2 Fe 0.2 Mn 0.4 The 0.05 Zr 0.15 O2、NaNi 0.2 Fe 0.3 Mn 0.4 The 0.09 Zr 0.01 O2、NaNi 0.2 Fe 0.29 Mn 0.4 Zn 0.1 Zr 0.01O2, NaNi 0.2 Fe 0.29 Mn 0.4 Mg 0.1 Zr 0.01 O2, NaNi 0.3 Fe 0.19 Mn 0.4 Cu 0.1 Zr 0.01 O2, NaNi 0.1 Fe 0.39 Mn 0.4 Cu 0.1 Zr 0.01 O2, NaFe 0.39 Mn 0.5 Cu 0.1 Zr 0.01 O2, NaNi 0.39 Fe 0.2 Mn 0.4 Zr 0.01 O2, NaNi 0.2 5Fe 0.39 Mn 0.3 Cu 0.05 Zr 0.01 O2, NaNi 0.39 Mn 0.5 Zn 0.1 Zr 0.01 O2, Na 0.7 Ni 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Zr 0.01 One or more of O2.
[0020] In some embodiments, the phase structure of the sodium ion layered oxide cathode material includes one or more of the following: O3 phase, O2 phase, P2 phase, and P3 phase.
[0021] In some embodiments, the space group of the sodium ion layered oxide cathode material includes R3-m, P63 / mmc One or more of them.
[0022] In different phase structures or space groups, Na + They have different coordination environments and contents, and the TMO6 structures have different interlayer spacings. TMO6 and Na + The different interactions between them affect the structural stability of layered oxides and the Na+ they can provide. + Content, Na +The extraction and insertion rates are improved. The embodiments of this application demonstrate improved water stability for sodium ion layered oxide cathode materials with different phase structures and space groups, exhibiting wide applicability.
[0023] Secondly, this application provides a positive electrode sheet, the positive electrode sheet including a positive active layer, the positive active layer comprising the above-mentioned sodium ion layered oxide positive electrode material.
[0024] The sodium-ion layered oxide cathode material of this application embodiment has multiple elemental co-doping properties and exhibits good water stability. Therefore, when this sodium-ion layered oxide cathode material is used as the cathode active material and applied to the cathode electrode, the cathode electrode can exhibit good structural stability during electrochemical cycling, thereby improving the electrochemical performance of the cathode electrode.
[0025] Thirdly, this application provides a battery, the battery including the above-mentioned positive electrode plate.
[0026] The aforementioned positive electrode sheet contains sodium-ion layered oxide positive electrode material, which is co-doped with multiple elements and exhibits good water stability. Therefore, applying this positive electrode sheet containing sodium-ion layered oxide positive electrode material to battery manufacturing reduces the battery's requirements for moisture content in storage and use environments. The battery can maintain good electrochemical performance even in aqueous environments; for example, it is less prone to significant capacity reduction in aqueous environments and can exhibit good cycle performance in aqueous environments.
[0027] Fourthly, this application provides an electrical device, which includes the aforementioned battery.
[0028] The battery disclosed in this application can be used in electrical devices that use batteries as a power source, or in various energy storage systems that use batteries as energy storage elements, to provide electrical energy. The positive electrode of the battery contains a sodium-ion layered oxide positive electrode material with excellent water stability, which can improve the battery's electrochemical performance, such as cycle stability. Therefore, using the battery described above can stably provide electrical energy to various electrical devices, improving the user experience of these devices. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 This is the crystal structure of the sodium ion layered oxide cathode material according to one embodiment of this application; Figure 2 The X-ray diffraction patterns of the sodium ion layered oxide cathode material of Comparative Example 1 of this application before and after immersion in water are shown. Figure b is an enlarged view of the diffraction angle of 16.0~16.5° in Figure a. Figure 3 The X-ray diffraction patterns of the sodium ion layered oxide cathode material of Example A1 of this application before and after immersion in water are shown. The diagram in Figure b is an enlarged view of the diffraction angle of 16.0~16.5° in Figure a. Figure 4 The X-ray diffraction patterns of the sodium ion layered oxide cathode material of Example B1 of this application before and after immersion in water are shown. The diagram in Figure b is an enlarged view of the diffraction angle of 16.0~16.5° in Figure a. Figure 5 The X-ray diffraction patterns of the sodium ion layered oxide cathode material of Example C1 of this application before and after immersion in water are shown. Figure b is an enlarged view of the diffraction angle of 16.0~16.5° in Figure a. Figure 6 This is a schematic diagram of a battery according to one embodiment of this application; Figure 7 for Figure 6 An exploded view of a battery according to one embodiment of this application is shown; Figure 8 This is a schematic diagram of a battery module according to one embodiment of this application; Figure 9 This is a schematic diagram of a battery pack according to one embodiment of this application; Figure 10 for Figure 9 An exploded view of a battery pack according to one embodiment of this application is shown; Figure 11 This is a schematic diagram of an electrical device in which a battery is used as a power source, according to one embodiment of this application.
[0031] Figure label: Housing 01 and cover 02, electrode assembly 03, battery cell 04, battery module 05, upper casing 06 and lower casing 07. Detailed Implementation
[0032] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0034] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0035] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0036] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0037] In the description of the embodiments of this application, the term "at least one" refers to one or more, and "more than one" refers to two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of a single item or a plurality of items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be a single item or multiple items.
[0038] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0039] The mass of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the masses of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass mentioned in the embodiments of this application can be a mass unit known in the chemical industry, such as µg, mg, g, kg.
[0040] Currently, lithium-ion batteries are the most widely used energy storage batteries. However, the low abundance of lithium resources in nature and high production costs have limited the development of lithium-ion batteries. Sodium-ion batteries, on the other hand, have attracted widespread attention and research due to the abundance and wide distribution of raw materials in nature, and hold promise for alleviating the problems of resource shortages and high production costs in energy storage batteries.
[0041] Cathode materials are key factors in achieving the high electrochemical performance of sodium-ion batteries, including high capacity, high voltage, and long cycle life. Currently, the most studied cathode materials for sodium-ion batteries include layered oxides, polyanionic compounds, and Prussian blue analogs. Among these, layered oxide cathode materials have become a research hotspot due to their higher specific capacity, superior performance, and simple synthesis compared to other cathode materials.
[0042] Research has found that nickel-iron-manganese base oxides, due to the presence of Ni and Fe elements, can achieve Ni... 2+ ~Ni 3+ ~Ni 4+ Due to the transfer of two electrons and the ability of Fe to provide charge compensation during the charging and discharging process, nickel-iron-manganese (Ni-Mn) base oxides exhibit high specific capacity. However, with low Ni and Fe content, Ni-Mn base oxides show low specific capacity at operating voltages above 2.5V. Furthermore, related studies indicate that the specific capacity of Ni-Mn base oxides increases with increasing Ni and Fe content. Therefore, to achieve high specific capacity in Ni-Mn base oxides, it is generally necessary to increase the Ni and Fe content. However, with high Ni and Fe content, Ni-Mn base oxides suffer from poor water stability, which easily degrades the performance of sodium-ion batteries and requires storage and use under harsher conditions, thus hindering the development of sodium-ion batteries.
[0043] The poor water stability of nickel-iron-manganese base oxides with high Ni and Fe content is mainly due to their strong surface hygroscopicity. Water easily dissociates on the surface of these oxides, leading to Na+ ionization. + / H +Exchange leads to a decrease in the Na content on the material surface. This decrease in surface Na content makes the material more susceptible to irreversible phase transitions, such as the layered-spinel-salt phase transition. This phase transition results in the formation of byproducts such as NiO and Fe3O4 on the cathode material surface, significantly reducing electrochemical properties such as capacity and surface impedance.
[0044] To address the poor water stability of nickel-iron-manganese (Ni-Mn) layered oxides with high Ni and Fe content, related technologies involve coating the surface of these oxides with materials such as carbon, titanium dioxide, alumina, or copper oxide to form a physical barrier between the sodium ion layered oxide cathode material and the external environment. However, during the coating process, the Ni-Mn layered oxide inevitably comes into contact with moisture in the air, leading to water absorption and changes in its crystal structure, which in turn affects the material's electrochemical performance. Furthermore, if the coating layer is damaged during later applications, the exposed Ni-Mn layered oxide will come into contact with water, causing various problems due to its poor water stability. Therefore, surface coating cannot fundamentally solve the problem of poor water stability in Ni-Mn layered oxides.
[0045] To address the aforementioned issues, embodiments of this application can significantly improve the water stability of nickel-iron-manganese base oxides by doping them with specific metal elements.
[0046] This layered oxide cathode material, which is doped with specific metal elements and has good water stability, can be used as a cathode active material to make cathode plates, and further applied to the manufacture of batteries and electrical devices.
[0047] The present application is further illustrated below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0048] Sodium-ion layered oxide cathode material The first aspect of this application provides a sodium-ion layered oxide cathode material, including Na... x Ni a Fe b Mn c M 1 d M 2 e O 2-p A p , where 0.6 < x M 1 Including one or more elements from groups IA to VA and groups IB to VIIB, M2 It includes one or more elements from Ga, Ta, and Zr, and A includes one or more nonmetallic elements from groups VIA and VIIA.
[0049] Groups IA through VA include groups IA, IIA, IIIA, IVA, and VA, which are the first to fifth main groups of the periodic table. The main elements include alkali metals, alkaline earth metals, and other metallic, semi-metallic, and non-metallic elements. Groups IB through VIIB include groups IB, IIB, IIIB, IVB, VB, VIB, and VIIB, which are the first to seventh subgroups of the periodic table. The main elements are transition metals.
[0050] This application embodiment involves doping a sodium ion layered oxide cathode material containing Ni and Fe with one or more elements selected from Ga, Ta, and Zr (M). 2 ),like Figure 1 The crystal structure of a sodium ion layered oxide cathode material is shown in the figure. Figure 1 M is not shown in the text. 1 (A, O), part of M 2 Elements occupy the surface positions of Ni and Fe in the sodium ion layered oxide cathode material, thus reducing the amount of Ni and Fe on the surface of the sodium ion layered oxide cathode material. These M elements... 2 The element itself is highly stable and does not readily coordinate with oxygen in water; therefore, M 2 Doping with elements can reduce the number of elements in sodium ion layered oxide cathode materials that can coordinate with oxygen contained in water, thereby improving the water stability of the material.
[0051] At the same time, in combination with Mn, M 1 By adjusting the proportions of each element, the thermodynamic energy of the reaction between sodium ion layered oxide cathode material and water increases, which means that the reaction between sodium ion layered oxide cathode material and water becomes more difficult, thereby enhancing the structural stability of sodium ion layered oxide cathode material and further improving its water stability.
[0052] In some implementations, M 1 Includes one or more of Cu, Li, Ti, K, Nb, Mg, Ca, Mo, Zn, Cr, W, Bi, Sn, Ge, Al, Si, P, and B. These metallic elements, or nonmetallic elements and half-metallic elements, are combined with M. 2 Co-doping with Ni and Fe increases the thermodynamic energy of the reaction between the sodium ion layered oxide cathode material and water, which helps to suppress the reaction between the sodium ion layered oxide cathode material and water and enhances the water stability of the sodium ion layered oxide cathode material.
[0053] In some embodiments, A includes one or more of F, Cl, and S. Doping oxygen sites in sodium ion layered oxide cathode materials with element A helps reduce oxygen defects in the crystal lattice and improves the structural stability of the sodium ion layered oxide cathode material.
[0054] In some implementations, 0.01 ≤ e ≤ 0.15, and optionally, 0.1 ≤ e ≤ 0.15. e may specifically include, but is not limited to, any one of 0.01, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, and 0.15, or a range between any two. e represents the atomic percentage of Ga, Ta, and Zr doping elements in the sodium ion layered oxide cathode material, and also reflects their doping amount. With appropriate Ga, Ta, and Zr doping amounts, the water stability of the sodium ion layered oxide cathode material can be effectively improved, while the negative impact on the capacity of the sodium ion layered oxide cathode material is relatively small.
[0055] In some implementations, optionally 0 < (a+b) / (c+d+e) ≤ 1.8, optionally 0 < (a+b) / (c+d+e) ≤ 1, and even more optionally 0.6 ≤ (a+b) / (c+d+e) ≤ 1. For example, (a+b) / (c+d+e) can be, but is not limited to, any one of the following values or a range between any two: 0.4, 0.5, 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.75, 0.8, 0.9, 0.95, 1, 1.5, 1.8, 2, 4, 6, 8, 10, 12, 14, 16, 18, 19. (a+b) / (c+d+e) can reflect the relationship between Ni and Fe, and Mn and Mn in the sodium ion layered oxide cathode material. 1 M 2 The ratios among the three, and under these ratios, Mn, M 1 M 2 It can effectively suppress the reaction between Ni and Fe and water, and enhance the water stability of sodium ion layered oxide cathode materials.
[0056] At the same time, for different M 2 Sodium-ion layered oxide cathode materials exhibit varying water stability depending on the value of (a+b) / (c+d+e). For example, for M... 2 In the case of one or both of Ga and Zr, sodium-ion layered oxide cathode materials with 0 < (a+b) / (c+d+e) ≤ 1.8, and optionally 0 < (a+b) / (c+d+e) ≤ 1, will have better water stability; for M 2 Including Ta, sodium-ion layered oxide cathode materials exhibit good water stability in the case of 0 < (a+b) / (c+d+e) ≤ 19.
[0057] In some implementations, 0.7≤ x ≤1, optionally 0.8≤ x ≤1. x It can include, but is not limited to, any one of the point values or any range of values between 0.65, 0.68, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.9, 0.92, 0.94, 0.96, 0.98, 1, 1.03, and 1.1. x This reflects the atomic percentage of Na in sodium-ion layered oxide cathode materials. Na ions are key active ions participating in electrochemical reactions in sodium-ion batteries, and their atomic percentage affects the capacity of sodium-ion layered oxide cathode materials. Simultaneously, Na interacts with other metal elements in the crystal structure, forming a stable layered structure. Therefore, with an appropriate Na percentage, sodium-ion layered oxide cathode materials exhibit both high capacity and a stable crystal structure.
[0058] At the same time, for different M 2 Sodium ion layered oxide cathode materials in x The water stability exhibited varies depending on the value of M. For example, for M... 2 In the case of one or both of Ga and Zr, 0.7 ≤ x Sodium ion layered oxide cathode materials with a concentration ≤1 will exhibit better water stability; for M 2 Including Ta, in the case of 0.6 < x Sodium-ion layered oxide cathode materials with a range of <1.2 all exhibit good water stability.
[0059] In some embodiments, 0 ≤ a ≤ 0.45, optionally, 0 ≤ a ≤ 0.4, and even more optionally, 0.1 ≤ a ≤ 0.3. For example, a can be, but is not limited to, any one of 0, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.24, 0.25, 0.26, 0.28, 0.3, 0.32, 0.34, 0.36, 0.38, 0.39, 0.4, 0.42, 0.45, or a range between any two. a reflects the atomic percentage of Ni in the sodium-ion layered oxide cathode material. At a certain Ni content, it helps to improve the specific capacity of the sodium-ion layered oxide cathode material, especially its specific capacity under high voltage. Meanwhile, in the sodium-ion layered oxide cathode material of this application embodiment, one or more elements selected from Ga, Ta, and Zr are combined with Mn and Mn... 1Together, they can suppress the reaction of Ni with water to form nickel oxide, as well as the side reaction with the electrolyte during electrochemical processes to form nickel oxide, thus exhibiting excellent water stability.
[0060] At the same time, for different M 2 Sodium-ion layered oxide cathode materials exhibit varying degrees of water stability depending on the value of 'a'. For example, for M... 2 In the case of Ga, sodium-ion layered oxide cathode materials with 0 ≤ a ≤ 0.39, especially 0 ≤ a ≤ 0.2, and optionally 0.1 ≤ a ≤ 0.2, exhibit good water stability; for M 2 Including Ta, sodium-ion layered oxide cathode materials exhibit excellent water stability in the wide range of 0 ≤ a ≤ 0.45; for M 2 Including Zr, sodium-ion layered oxide cathode materials with 0 ≤ a ≤ 0.39 and optionally 0.1 ≤ a ≤ 0.3 exhibit good water stability.
[0061] In some embodiments, 0 ≤ b ≤ 0.5, optionally, 0.19 ≤ b ≤ 0.39, and even more optionally, 0.3 ≤ b ≤ 0.39. For example, b can be, but is not limited to, any one of 0, 0.01, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or a range between any two. b reflects the atomic percentage of Fe in the sodium ion layered oxide cathode material. At a certain Fe content, it helps to improve the specific capacity of the sodium ion layered oxide cathode material, especially to improve the specific capacity of the sodium ion layered oxide cathode material under high voltage. Meanwhile, in the sodium ion layered oxide cathode material of the embodiments of this application, one or more elements selected from Ga, Ta, and Zr are combined with Mn and Mn. 1 Together, they can suppress the reaction of Fe with water to form iron oxides, as well as the side reaction with the electrolyte during electrochemical processes to form iron oxides, thus exhibiting excellent water stability.
[0062] For different M 2 Sodium-ion layered oxide cathode materials exhibit varying degrees of water stability depending on the value of b. For example, for M... 2 In the case of Ga, sodium-ion layered oxide cathode materials with 0.2 ≤ b ≤ 0.39, and optionally 0.3 ≤ b ≤ 0.39, exhibit good water stability; for M 2 Including Ta, sodium-ion layered oxide cathode materials exhibit excellent water stability in the wide range of 0 ≤ b ≤ 0.5; for M 2Including Zr, sodium-ion layered oxide cathode materials with 0.19 ≤ b ≤ 0.39 exhibit good water stability.
[0063] In some implementations, 0 ≤ c ≤ 0.5, optionally 0 ≤ c ≤ 0.4, or 0.3 ≤ c ≤ 0.5. For example, c can be, but is not limited to, any one of 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or a range between any two. c can reflect the atomic percentage of Mn in the sodium-ion layered oxide cathode material. Under a suitable atomic percentage, Mn can interact with Ga, Ta, Zr, and Mn. 1 The elements work together to improve the water stability of sodium ion layered oxide cathode materials. Meanwhile, Mn has a significant impact on improving the capacity of sodium ion layered oxide cathode materials.
[0064] For different M 2 Sodium-ion layered oxide cathode materials exhibit varying degrees of water stability depending on the value of c. For example, for M... 2 In the case of Ga, sodium-ion layered oxide cathode materials exhibit good water stability when 0 < c, optionally 0.3 ≤ c ≤ 0.5, and further optionally 0.4 ≤ c ≤ 0.5; for M 2 Including Ta, sodium-ion layered oxide cathode materials exhibit excellent water stability in the wide range of 0 ≤ c, optionally 0 ≤ c ≤ 0.5; for M 2 Including Zr, sodium-ion layered oxide cathode materials with 0 < c, and optionally 0.3 ≤ c ≤ 0.5, exhibit good water stability.
[0065] In some implementations, 0 ≤ d ≤ 0.2; alternatively, 0 ≤ d ≤ 0.1; and further alternatively, 0.05 ≤ d ≤ 0.1. For example, d can be, but is not limited to, any one of the following point values or a range between any two: 0, 0.01, 0.02, 0.04, 0.05, 0.06, 0.08, 0.09, 0.1, 0.12, 0.14, 0.16, 0.18, and 0.2. d can reflect M. 1 In sodium-ion layered oxide cathode materials, the atomic percentage, under a suitable atomic percentage, is M 1 It can work with Ga, Ta, Zr and Mn to improve the water stability of sodium ion layered oxide cathode materials.
[0066] In some implementations, 1.5 ≤ p ≤ 2. For example, p can be any point value among 1.5, 1.52, 1.54, 1.56, 1.58, and 2, or a range of values between any two.
[0067] In some implementations, 0 ≤ q ≤ 0.05. For example, q can be any point value or a range of any two of 0, 0.01, 0.02, 0.04, 0.05, 0.06, 0.08, and 0.1. q It can reflect the atomic ratio of A in sodium ion layered oxide cathode materials. Under a suitable atomic ratio, A can reduce oxygen vacancies in sodium ion layered oxide cathode materials, improve the stability of oxygen, and thus help improve the electrochemical cycle performance of sodium ion layered oxide cathode materials.
[0068] In some implementations, M 2 The proportions of elements in Ga and sodium ion layered oxide cathode materials are as follows: 0.7≤ x ≤1, optionally 0.8≤ x ≤1; 0 ≤ a ≤ 0.39, optionally 0 ≤ a ≤ 0.2, and further optionally 0.1 ≤ a ≤ 0.2; 0 < b, optionally 0.2 ≤ b ≤ 0.39, and further optionally 0.3 ≤ b ≤ 0.39; 0 < c, optionally 0.3 ≤ c ≤ 0.5, and further optionally 0.4 ≤ c ≤ 0.5; 0 ≤ d, optionally 0 ≤ d ≤ 0.1, and further optionally 0.05 ≤ d ≤ 0.1; 0 < e ≤ 0.15, optionally 0.01 ≤ e ≤ 0.15, and further optionally 0.1 ≤ e ≤ 0.15; a+b+c+d+e=1; 0 < (a+b) / (c+d+e) ≤ 1.8, optionally 0 < (a+b) / (c+d+e) ≤ 1, and further optionally 0.6 ≤ (a+b) / (c+d+e) ≤ 1.
[0069] In some implementations, M 2 The proportions of elements in the sodium ion layered oxide cathode material, including Ta, are as follows: 0.6 < x <1.2, 0.7≤ x ≤1; 0 ≤ a, optionally 0 ≤ a ≤ 0.45; 0 ≤ b, optionally 0 ≤ b ≤ 0.5; 0≤c≤0.5, optionally 0≤c≤0.4; 0 ≤ d, optionally 0 ≤ d ≤ 0.1; 0 < e ≤ 0.15, optionally 0.01 ≤ e ≤ 0.15, and further optionally 0.1 ≤ e ≤ 0.15; a+b+c+d+e=1; 0 < (a+b) / (c+d+e) ≤ 19, optionally 0.6 ≤ (a+b) / (c+d+e) ≤ 19.
[0070] In some implementations, M 2 The proportions of elements in the sodium ion layered oxide cathode material, including Zr, are as follows: 0.7≤ x ≤1, optionally 0.8≤ x ≤1; 0 ≤ a ≤ 0.39, optionally 0.1 ≤ a ≤ 0.3; 0 < b, optionally 0.19 ≤ b ≤ 0.39; 0 < c, optionally 0.3 ≤ c ≤ 0.5; 0 ≤ d, optionally 0 ≤ d ≤ 0.1; 0 < e ≤ 0.15, optionally 0.01 < e ≤ 0.15, optionally 0.1 ≤ e ≤ 0.15; a+b+c+d+e=1; 0 < (a+b) / (c+d+e) ≤ 1.8, optionally 0 < (a+b) / (c+d+e) ≤ 1, and further optionally 0.6 ≤ (a+b) / (c+d+e) ≤ 1.
[0071] Ga, Ta, Zr three kinds of M 2 Doping with any of the three elements can improve the structure of sodium-ion layered oxide cathode materials, thereby enhancing their water stability. However, the effects of the three elements on improving the water stability of sodium-ion layered oxide cathode materials also vary. When using different M... 2 In this case, by adaptively adjusting and optimizing the proportions of various elements in the sodium ion layered oxide cathode material, it is possible to fully utilize the different M... 2 It enhances water stability.
[0072] In some embodiments, the sodium-ion layered oxide cathode material includes NaNi. 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Ga 0.01 O2, NaNi 0.2 Fe 0.2 Mn 0.4 Cu 0.05 Ga 0.15 O2, NaNi 0.2 Fe 0.3 Mn 0.4 Cu 0.09 Ga 0.01 O2, NaNi 0.2 Fe 0.29Mr 0.4 Zn 0.1 Ga 0.01 O2、NaNi 0.2 Feb 0.3 0Mn 0.4 Mg 0.05 Ga 0.0 5O2、NaNi 0.1 Feb 0.39 Mr 0.4 Cu 0.1 Ga 0.01 O2、NaFe 0.39 Mr 0.5 Cu 0.1 Ga 0.01 O2、NaNi 0.39 Feb 0.2 Mr 0.4 Ga 0.01 O2、NaNi 0.25 Feb 0.39 Mr 0.3 Cu 0.05 Ga 0.01 O2、Na 0.7 Ni 0.2 Feb 0.29 Mr 0.4 Cu 0.1 Ga 0.01 O2、NaNi 0.2 Feb 0.29 Mr 0.4 Cu 0.1 Dad 0.01 O2、NaNi 0.2 Feb 0.2 Mr 0.4 Cu 0.05 Dad 0.15 O2、NaNi 0.3 Feb 0.3 Mr 0.4 Cu 0.09 Dad 0.01 O2、NaNi 0.2 Feb 0.29 Mr 0.4 Zn 0.1 Dad 0.01 O2、NaNi 0.2 Feb 0.30 Mr 0.4 Mg 0.05 Dad 0.0 5O2、NaNi 0.3 Feb 0.19 Mr 0.4 Cu 0.1 Dad 0.01 O2、NaNi0.1 Fe 0.39 Mn 0.4 The 0.1 Ta 0.01 O2、NaFe 0.39 Mn 0.5 The 0.1 Ta 0.01 O2、NaNi 0.39 Mn 0.5 Zn 0.1 Ta 0.01 O2、NaNi 0.45 Fe 0.5 The 0.04 Ta 0.01 O2、NaNi 0.39 Fe 0.2 Mn 0.4 Ta 0.01 O2、Na 1.03 Aunt 0.2 Fe 0.29 Mn 0.4 The 0.1 Ta 0.01 O2、Na 0.7 Aunt 0.2 Fe 0.29 Mn 0.4 The 0.1 Ta 0.01 O2、NaNi 0.25 Fe 0.39 Mn 0.3 The 0.05 Ta 0.01 O2、NaNi 0.2 Fe 0.29 Mn 0.4 The 0.1 Zr 0.01 O2、NaNi 0.2 Fe 0.2 Mn 0.4 The 0.05 Zr 0.15 O2、NaNi 0.2 Fe 0.3 Mn 0.4 The 0.09 Zr 0.01 O2、NaNi 0.2 Fe 0.29 Mn 0.4 Zn 0.1 Zr 0.01 O2、NaNi 0.2 Fe 0.29 Mn 0.4 Mg 0.1 Zr 0.01O2, NaNi 0.3 Fe 0.19 Mn 0.4 Cu 0.1 Zr 0.01 O2, NaNi 0.1 Fe 0.39 Mn 0.4 Cu 0.1 Zr 0.01 O2, NaFe 0.39 Mn 0.5 Cu 0.1 Zr 0.01 O2, NaNi 0.39 Fe 0.2 Mn 0.4 Zr 0.01 O2, NaNi 0.2 5Fe 0.39 Mn 0.3 Cu 0.05 Zr 0.01 O2, NaNi 0.39 Mn 0.5 Zn 0.1 Zr 0.01 O2, Na 0.7 Ni 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Zr 0.01 One or more of O2.
[0073] In some embodiments, the phase structure of the sodium-ion layered oxide cathode material includes one or more of the following: O3 phase, O2 phase, P2 phase, and P3 phase. The sodium-ion layered oxide cathode material can have a single phase structure or a composite of multiple phase structures. Optionally, the phase structure of the sodium-ion layered oxide cathode material includes an O3 phase.
[0074] In some embodiments, the space group of the sodium ion layered oxide cathode material includes R3-m, P63 / mmc One or more of them.
[0075] Layered oxides are composed of TMO6 (TM represents transition metals, alkaline earth metals, or other elements in the layered oxide; in the sodium ion layered oxide cathode material of this application embodiment, TM includes Mn, Fe, Ni, M 1 and M 2 It is composed of stacked layers, Na + Interlayer embedding and extraction in TMO6 stacks. According to Na... + Depending on the coordination environment, the phase structure of layered oxides can be divided into O phase and P phase; O represents Na. +It is octahedral coordination, Na + Occupying an octahedral point; P represents Na + It is a prismatic coordination, Na + It occupies a position on a triangular prism. In the crystal structure, Na + The TMO6 structure is connected in the O phase via edge sharing, and in the P phase via both surface sharing and edge sharing.
[0076] Based on the stacking sequence of oxygen layers, layered oxides can be further divided into P2 phase, O2 phase, P3 phase, and O3 phase. The stacking pattern for P2 is ABBA, for O2 it is ABAC (or ABCB), for P3 it is ABBCCA, and for O3 it is ABCABC. The numbers "2" and "3" represent the number of transition metal layers of different types of oxygen stacked in each unit.
[0077] Different phase structures correspond to different space groups. For example, the space group corresponding to the O3 phase structure is R3-m, and the space group corresponding to the P2 phase structure is P63 / mmc .
[0078] Phase structure and space group can be obtained through X-ray powder diffraction analysis. For example, by testing a sample with an X-ray powder diffractometer, the X-ray diffraction pattern of the sample can be obtained. By comparing the XRD diffraction peaks in the X-ray diffraction pattern with the standard cards of the XRD analysis software, the phase structure and space group of the sample can be confirmed.
[0079] In different phase structures or space groups, Na + They have different coordination environments and contents, and the metal layers (TMO6 layers) have different interlayer spacings. TMO6 and Na + The different interactions between them affect the structural stability of layered oxides and the Na+ they can provide. + Content, Na + The extraction and insertion rates are improved. The embodiments of this application demonstrate improved water stability for sodium ion layered oxide cathode materials with different phase structures and space groups, exhibiting wide applicability.
[0080] In some embodiments, the interlayer spacing of the sodium-ion layered oxide cathode material is 0.4~0.6 nm, optionally 0.5~0.6 nm, for example, it can be any one of 0.4 nm, 0.42 nm, 0.44 nm, 0.46 nm, 0.48 nm, 0.5 nm, 0.52 nm, 0.54 nm, 0.56 nm, 0.58 nm, 0.6 nm, or a range between any two. The interlayer spacing of the sodium-ion layered oxide cathode material refers to the distance between the metal layers (TMO6 layers), which can be understood as the distance between adjacent oxygen atom layers on both sides of the sodium layer. This interlayer spacing can be obtained by acquiring the X-ray diffraction information of the sodium-ion layered oxide cathode material and calculating it by combining the peak position of the (003) crystal plane with the Bragg equation. + Interlayer embedding and extraction in TMO6 stacks, while Na + The ionic radius is around 0.096 nm, therefore a suitable interlayer spacing can provide Na + Rapid insertion and extraction are beneficial for improving Na + This improves the transport rate and enhances the electrochemical performance of sodium ion layered oxide cathode materials.
[0081] In some embodiments, the Dv50 of the sodium ion layered oxide cathode material is 10~30μm, optionally 10~20μm, for example, it can be any one of 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 25μm, 26μm, 28μm, 30μm or any range between two.
[0082] The particle size distribution of materials is usually expressed as the percentage of particles within different size ranges relative to the total particle size. There are various benchmarks for determining particle size distribution, such as number distribution, length distribution, area distribution, volume distribution, and weight distribution. Dv50 is a specific particle size distribution based on volume distribution, also known as the median particle size. It refers to the particle size at which the cumulative volume distribution of particles reaches 50%, indicating that 50% of the particles have a diameter exceeding this value, and 50% of the particles have a diameter below this value. The Dv50 of particles can be obtained by referring to GB / T 19077-2016 / ISO 13320:2009 "Particle size distribution - Laser diffraction method". In the embodiments of this application, the particle morphology of the sodium ion layered oxide cathode material can be a regular sphere, an ellipsoid, a polygon, or other irregular shapes. For spherical particles, the particle size is its diameter; for non-spherical or other irregularly shaped particles, the particle size is its equivalent diameter. The sodium-ion layered oxide cathode material of this application embodiment has a suitable Dv50, which is beneficial for applying the sodium-ion layered oxide cathode material to the preparation of uniform cathode slurry; and the micron-level median particle size has lower requirements for the preparation process, which helps to control costs.
[0083] In some embodiments, the specific surface area of the sodium ion layered oxide cathode material is 0.1~5 m². 2 / g, optionally 0.3~3m 2 / g, for example, may include but is not limited to 0.1m 2 / g, 0.3m 2 / g, 0.5m 2 / g, 1m 2 / g, 1.5m 2 / g、2m 2 / g, 2.5m 2 / g、3m 2 / g, 3.5m 2 / g、4m 2 / g, 4.5m 2 / g、5m 2 The specific surface area can be any one of the values in / g or a range between any two. Specific surface area can be determined using the nitrogen adsorption specific surface area analysis method, referring to GB / T 19587-2017 "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method". A suitable specific surface area range helps to achieve higher specific capacity, initial coulombic efficiency, and cycle life.
[0084] In some embodiments, the tap density of the sodium ion layered oxide cathode material is 1~3 g / cm³. 3 The optional concentration is 1.5~2.5 g / cm³. 3 For example, it can include, but is not limited to, 1g / cm³ 3 1.2g / cm3 1.4g / cm 3 1.5g / cm 3 1.6g / cm 3 1.8g / cm 3 2g / cm 3 2.2g / cm 3 2.4g / cm 3 2.5g / cm 3 2.6g / cm 3 2.8g / cm 3 3g / cm 3 The tap density refers to the density of powder in a container after it has been tapped under specified conditions. Tap density reflects properties such as powder flowability and porosity. For example, tap density can be measured using a tap density meter according to GB / T 5162-2021, "Determination of Tap Density of Metal Powders". A higher tap density means that, in the process of using sodium ion layered oxide cathode material to manufacture cathode sheets, a higher quality sodium ion layered oxide cathode material can store more sodium ions in the same volume, thus increasing the energy density of the electrode. In other words, tap density affects the energy density of the electrode. Simultaneously, tap density also reflects the porosity of the powder. With appropriate porosity, the electrode has good electrolyte wetting properties, facilitating sodium ion transport. The sodium ion layered oxide cathode material in the embodiments of this application has a suitable tap density, which not only helps improve the energy density of the electrode but also improves its electrolyte wetting properties and accelerates sodium ion transport.
[0085] In some embodiments, the powder compaction density of the sodium ion layered oxide cathode material under 8 tons of pressure is 3~5 g / cm³. 3 The optional concentration is 3.5~4.5 g / cm³. 3 For example, it can include, but is not limited to, 3g / cm³ 3 3.2g / cm 3 3.4g / cm 3 3.5g / cm 3 3.6g / cm 3 3.8g / cm 3 4g / cm 3 4.2g / cm 3 4.4g / cm 3 4.5g / cm 3 4.6g / cm 3 4.8g / cm 3 5g / cm 3The compaction density is any one of the point values or any range between two values. Compacted density is the density of powder under a certain pressure; compacted density = areal density / material thickness. Compacted density can be obtained by referring to relevant standards, such as Appendix L of GB / T 24533-2019, "Test Method for Powder Compacted Density," using a compaction density meter. Compacted density affects the energy density, electrolyte wetting performance, and sodium ion transport rate of the electrode. A higher compaction density results in a higher mass of sodium ion layered oxide cathode material per unit volume, which is beneficial for improving the electrode's energy density. Simultaneously, compacted density also reflects the electrode's porosity. At a suitable porosity, the electrode exhibits excellent electrolyte wetting performance, facilitating sodium ion transport. The sodium ion layered oxide cathode material in the embodiments of this application has a suitable compaction density, which not only improves the electrode's energy density but also enhances its electrolyte wetting performance and accelerates sodium ion transport.
[0086] Preparation of sodium-ion layered oxide cathode materials The sodium-ion layered oxide cathode material of this application embodiment can be prepared by one or more of the solid-state method and co-precipitation method. The specific preparation method can be found in the following content.
[0087] 1. Solid-phase method Sodium ion layered oxide cathode materials can be prepared by a solid-state method, which includes: According to Na x Ni a Fe b Mn c M 1 d M 2 e O 2-p A p The atomic ratio, with Na source, Mn source, Fe source, Ni source, M 1 Source, M 2 Source A and source A are calcined together to obtain sodium ion layered oxide cathode material; Where, 0.6 < x M 1 Including one or more elements from groups IA to VA and groups IB to VIIB, M 2 It includes one or more elements from Ga, Ta, and Zr, and A includes one or more nonmetallic elements from groups VIA and VIIA.
[0088] By employing a solid-state method to co-calcine various raw materials, sodium-ion layered oxide cathode materials with multiple elemental doping can be obtained. This preparation method is simple and suitable for large-scale production. The resulting sodium-ion layered oxide cathode material is simultaneously doped with M... 1 Mn, M 2 Multiple elements, with appropriate elemental content and proportions, on the one hand, some M 2 Elements occupy the surface positions of Ni and Fe in the sodium ion layered oxide cathode material, thus reducing the amount of Ni and Fe on the surface of the sodium ion layered oxide cathode material. These M elements... 2 The element itself is highly stable and does not readily coordinate with oxygen in water; therefore, M 2 Doping with elements can reduce the number of elements in sodium-ion layered oxide cathode materials that can coordinate with oxygen contained in water, thereby improving the water stability of the material. On the other hand, the thermodynamic energy of the reaction between the sodium-ion layered oxide cathode material and water is increased, that is, the reaction between the sodium-ion layered oxide cathode material and water is more difficult, thereby enhancing the structural stability of the sodium-ion layered oxide cathode material and further improving its water stability.
[0089] In some embodiments, the calcination temperature is 600~1200℃, optionally 800~1000℃, for example, including but not limited to any one of 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, and 1200℃, or a range between any two. The holding time at the calcination temperature is 10~20h, optionally 10~15h, for example, including but not limited to any one of 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, and 20h, or a range between any two. The calcination temperature and the holding time at that temperature can be directly set and controlled on the calcination equipment, such as a muffle furnace. Under suitable calcination temperature and time, the raw materials can be fully melted, mixed and reacted to form composite metal oxides.
[0090] In some embodiments, the heating rate during the calcination process is 2~10℃ / min, optionally 3~5℃ / min, for example, including but not limited to any one of 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, and 10℃ / min, or a range between any two. Here, the heating rate refers to the rate of temperature change during the process of heating to the required calcination temperature. The heating rate is one of the key factors affecting the grain size and morphology of the material. At the heating rate of the embodiments of this application, the sodium ion layered oxide cathode material can have a suitable particle size and a complete grain morphology.
[0091] After calcination, the product can be cooled down naturally.
[0092] In some embodiments, the preparation method of sodium ion layered oxide cathode material may optionally include a pre-calcination treatment step. The temperature of the pre-calcination treatment can be set to 600-900℃, optionally 800-900℃, for example, including but not limited to any one of 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, and 900℃, or a range between any two. The holding time at the pre-calcination treatment temperature is 10-20 hours, optionally 10-15 hours, for example, including but not limited to any one of 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, and 20 hours, or a range between any two. The pre-calcination treatment step can be performed before the calcination treatment step. Pre-calcination involves pre-treating the raw material at a temperature lower than the final calcination temperature before the final calcination. Pre-calcining the raw materials helps remove impurities and improve the purity of the product; it also helps improve the crystal morphology of the product.
[0093] The calcination and pre-calcination processes described above can both be carried out in an air or oxygen atmosphere.
[0094] In some embodiments, the preparation method of sodium ion layered oxide cathode material further includes using Na source, Mn source, Fe source, Ni source, and Mn source. 1 Source, M 2 The process involves mixing the raw materials A and B. The mixing methods include, but are not limited to, one or more of mechanical stirring, grinding, and ball milling. For example, grinding can be performed first, followed by ball milling. These mixing steps not only ensure uniform mixing of the various raw materials but also reduce their particle size, facilitating the calcination preparation of sodium ion layered oxide cathode materials with the desired particle size.
[0095] In the solid-state method, Na source, Mn source, Fe source, Ni source, M 1 Source, M 2 Source A and Source B can each be independently selected from either soluble or non-soluble compounds. For example, the specific types of compounds that can be selected for each raw material are as follows: Sodium sources include, but are not limited to, one or more of Na2CO3, NaHCO3, NaOH, Na2O2, and other sodium salts; Ni sources include, but are not limited to, one or more of NiO and Ni(OH)2; Fe sources include, but are not limited to, one or more of Fe2O3, Fe3O4, and FeO; Mn sources include, but are not limited to, one or more of Mn2O3, Mn3O4, MnO, and MnO2; M 1 Sources include, but are not limited to, those containing M 1 oxides, containing M 1 hydroxides, containing M 1 carbonates, containing M 1 One or more of the bicarbonates; M 2 Sources include, but are not limited to, those containing M 2 oxides, containing M 2 hydroxides, containing M 2 carbonates, containing M 2 One or more of the bicarbonates; The source of A includes, but is not limited to, one or more of metal A compounds and metal A salts, wherein the metal A compounds and metal A salts contain metal elements including Na, Fe, Mn, Ni, and M. 1 M 2 One or more of these elements; to reduce the negative impact of other metal elements on the performance of sodium-ion layered oxide cathode materials, Na, Fe, Mn, Ni, and M should be avoided as much as possible in the A source. 1 M 2 Other metallic elements.
[0096] 2. Coprecipitation method Sodium ion layered oxide cathode materials can also be prepared by co-precipitation, which may include: Provides Mn source, Fe source, Ni source, M 1 Source, M 2 A mixed solution of source A and source B was subjected to co-precipitation treatment to obtain the precursor; The precursor and Na source were calcined to obtain a sodium ion layered oxide cathode material. Among them, Na, Mn, Fe, Ni, M 1M 2 The molar ratio of A satisfies Na x Ni a Fe b Mn c M 1 d M 2 e O 2-p A p 0.6 < x <1.2, 0≤a, 0≤b, 0≤c, 0≤d, 0<e≤0.15, a+b+c+d+e=1, 0<(a+b) / (c+d+e)≤19, 0≤ p ≤0.1; M 1 Including one or more elements from groups IA to VA and groups IB to VIIB, M 2 It includes one or more elements from Ga, Ta, and Zr, and A includes one or more nonmetallic elements from groups VIA and VIIA.
[0097] By employing a co-precipitation method, elements other than Na are first co-precipitated to obtain a precursor, which is then calcined with a Na source to obtain a sodium-ion layered oxide cathode material with multiple elemental co-doping. This preparation method is simple and suitable for large-scale production. The resulting sodium-ion layered oxide cathode material is also doped with M. 1 Mn, M 2 Multiple elements, with appropriate elemental content and proportions, on the one hand, some M 2 Elements occupy the surface positions of Ni and Fe in the sodium ion layered oxide cathode material, thus reducing the amount of Ni and Fe on the surface of the sodium ion layered oxide cathode material. These M elements... 2 The element itself is highly stable and does not readily coordinate with oxygen in water; therefore, M 2 Doping with elements can reduce the number of elements in sodium-ion layered oxide cathode materials that can coordinate with oxygen contained in water, thereby improving the water stability of the material. On the other hand, the thermodynamic energy of the reaction between the sodium-ion layered oxide cathode material and water is increased, that is, the reaction between the sodium-ion layered oxide cathode material and water is more difficult, thereby enhancing the structural stability of the sodium-ion layered oxide cathode material and further improving its water stability.
[0098] In some embodiments, the coprecipitation treatment step includes reacting the mixed solution with a precipitant. The precipitant includes a compound containing one or more ions selected from hydroxide ions, carbonate ions, and oxalate ions. In practice, the mixed solution can be mixed with the precipitant, or the mixed solution can be mixed with a solution containing the precipitant, and then a precipitation reaction can occur spontaneously.
[0099] In the coprecipitation method, Mn source, Fe source, Ni source, M 1 Source, M 2 Source A and Source B can each independently select their respective soluble compounds, optionally including their respective water-soluble compounds. For example, the specific types of compounds that can be selected for each raw material are as follows: The Ni source can be one or more of Ni chloride, Ni sulfate, and Ni nitrate; The Fe source can be one or more of Fe chloride, Fe sulfate, and Fe nitrate; The Mn source can be one or more of the following, including but not limited to Mn chloride, Mn sulfate, and Mn nitrate; M 1 Sources may include, but are not limited to, M 1 Chloride, M 1 sulfates, M 1 One or more of the nitrates; M 2 Sources may include, but are not limited to, M 2 Chloride, M 2 sulfates, M 2 One or more of the nitrates; The source A can be one or more of metal A compounds and metal A salts, wherein the metal A compounds and metal A salts contain metal elements including Na, Fe, Mn, Ni, and M. 1 M 2 One or more of these elements; to reduce the negative impact of other metal elements on the performance of sodium-ion layered oxide cathode materials, Na, Fe, Mn, Ni, and M should be avoided as much as possible in the A source. 1 M 2 Other metallic elements.
[0100] For the Na source, either a soluble or non-soluble compound of Na can be selected, such as, but not limited to, one or more of Na2CO3, NaHCO3, NaOH, Na2O2, and other sodium salts.
[0101] It should be understood that, corresponding to the types of raw materials mentioned above, the solvent in the mixed solution should have the ability to dissolve these raw materials. For example, the solvent may include one or more of water and ethanol, and optionally water.
[0102] In the coprecipitation method, the calcination temperature, time, and heating rate are the same as in the solid-state method. Alternatively, a pre-calcination step can be added before the calcination treatment, with the same temperature and time as in the solid-state method. Both the calcination and pre-calcination steps can be carried out in an air or oxygen atmosphere.
[0103] In addition, before calcination (or pre-calcination), the process may include a step of mixing the precursor with the Na source. The mixing method includes, but is not limited to, one or more of mechanical stirring, grinding, and ball milling. For example, grinding may be performed first, followed by ball milling.
[0104]
Positive Electrode
[0105] The sodium-ion layered oxide cathode material of this application embodiment has multiple elemental co-doping properties and exhibits good water stability. Therefore, when this sodium-ion layered oxide cathode material is used as the cathode active material and applied to the cathode electrode, the cathode electrode can exhibit good structural stability during electrochemical cycling, thereby improving the electrochemical performance of the cathode electrode.
[0106] In some embodiments, the mass content of sodium ion layered oxide cathode material in the cathode active layer is 50% to 98%, optionally 80% to 95%, for example, it can be any one of 50%, 55%, 60%, 65%, 70%, 75%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, or any range between two values. The sodium ion layered oxide cathode material can be the sole cathode active material in the cathode electrode sheet, or it can be blended with other cathode active materials in a certain proportion or distributed together in a certain manner in the cathode active layer. Other cathode active materials can include one or more of layered oxide cathode materials of other compositions, Prussian blue cathode materials, and polyanionic cathode materials. Therefore, the mass content of sodium ion layered oxide cathode material in the cathode active layer can be determined according to the actual situation. It is understood that a high mass content of sodium ion layered oxide cathode material in the cathode active layer will help improve the structural stability of the cathode electrode sheet.
[0107] In some embodiments, the positive electrode active layer further includes one or more of a conductive agent and a binder. The conductive agent is used to collect microcurrents between the active materials and between the active materials and the current collector, thereby improving electronic conductivity. The conductive agent also promotes the wetting of the positive electrode sheet by the electrolyte. The binder enhances the bonding strength between the substances in the active layer and between the active layer and the current collector.
[0108] In some embodiments, the mass content of the conductive agent in the positive electrode active layer is 0.5% to 10%, optionally 1% to 7%, for example, any one of 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, or a range between any two, or other contents may be set as needed.
[0109] In some embodiments, the conductive agent includes one or more of acetylene black (SP), carbon nanotubes, conductive carbon black (super-P), Ketjen black, carbon fiber, and graphene.
[0110] In some embodiments, the mass content of the binder in the positive electrode active layer is 0.5% to 15%, optionally 1% to 7%, for example, any one of 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any range between two, or it can be set to other contents as needed.
[0111] In some embodiments, the adhesive includes, but is not limited to, one or more of the following: polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyimide, polytetrafluoroethylene, polybutyl acrylate, polyacrylonitrile, carboxymethyl cellulose, carboxymethyl cellulose salt, polyacrylic acid, polyacrylate, polyvinyl alcohol, sodium alginate, cyclodextrin, styrene-butadiene rubber, vinyl acetate resin, acrylic resin, and chlorinated rubber.
[0112] In some embodiments, the positive electrode active layer may optionally include a thickener, such as carboxymethyl cellulose (CMC). The mass content of the thickener in the positive electrode active layer can be set to 0.5% to 5%, optionally 1% to 5%, including but not limited to any one of 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%, or a range between any two. The thickener helps to increase the viscosity of the positive electrode slurry and improve its processing performance.
[0113] In some embodiments, the positive electrode active layer may optionally include a sodium-replenishing additive, such as one or more of transition metal sodium salts, sodium azide, sodium squartz salts, and Prussian blue sodium salts. The mass content of the sodium-replenishing additive in the positive electrode active layer can be set to 0.1% to 20%, for example, any one of 0.1%, 0.5%, 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, or 20%, or a range between any two. The sodium-replenishing additive can release sodium ions during the electrochemical reaction, replenishing the sodium ions lost by the positive electrode active material during battery charging and discharging, thereby improving battery capacity and lifespan.
[0114] In some embodiments, the positive electrode further includes a positive current collector, and the positive active layer is disposed on at least one side of the positive current collector. The current collector is used to transport electrons. In the embodiments of this application, the positive current collector may include, but is not limited to, metal current collectors, carbon current collectors, conductive resin current collectors, composite current collectors of metal and resin, etc., and more specifically, aluminum, copper, nickel, titanium, iron and their respective alloys, stainless steel, carbon fiber, carbon nanotubes (CNTs), graphite, etc. Optionally, the positive current collector includes aluminum.
[0115] The positive electrode sheet of this application embodiment can be manufactured through processes such as pulping, coating, drying, and compaction.
[0116] For example, the positive electrode sheet can be made as follows: Sodium ion layered oxide cathode material, conductive agent, binder (thickener or other cathode active materials and other additives may also be added as needed) are mixed with solvent to obtain cathode slurry; The positive electrode slurry is coated onto the current collector, dried, and compacted to obtain the positive electrode sheet.
[0117] The solvent may include, but is not limited to, N-methylpyrrolidone (NMP). The compaction method may include one or more of hot pressing and cold pressing, and the pressure used in the compaction step may be determined according to the target compaction density.
[0118]
Battery
[0119] A third aspect of this application provides a battery comprising the aforementioned positive electrode plate.
[0120] Depending on the packaging form, batteries are classified into individual battery cells, battery modules, and battery packs. The batteries in this application embodiment include one or more of the following: individual battery cells, battery modules, and battery packs.
[0121] The aforementioned positive electrode sheet contains sodium-ion layered oxide positive electrode material, which is co-doped with multiple elements and exhibits good water stability. Therefore, applying this positive electrode sheet containing sodium-ion layered oxide positive electrode material to battery manufacturing reduces the battery's requirements for moisture content in storage and use environments. The battery can maintain good electrochemical performance even in aqueous environments; for example, it is less prone to significant capacity reduction in aqueous environments and can exhibit good cycle performance in aqueous environments.
[0122] Typically, a battery includes a positive electrode, a negative electrode, an electrolyte, a separator, and may also include outer packaging or other components. The following describes the components of a battery other than the positive electrode.
[0123] 1. Negative electrode plate In a battery, the negative electrode is typically isolated from the positive electrode. The negative electrode includes a negative current collector and optionally a negative active layer disposed on at least one side of the negative current collector, the negative active layer containing a negative active material.
[0124] The negative electrode current collector can be, but is not limited to, a metal or a composite current collector. For example, as a metal, sodium, sodium alloys, copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, silver alloys, etc., can be used. When sodium or sodium alloys are used as the negative electrode current collector, since sodium or sodium alloys themselves can also serve as the negative electrode active material, the negative electrode sheet may not contain a negative electrode active layer; sodium or sodium alloys are both the current collector and the negative electrode active material.
[0125] Composite current collectors can be composite materials of polymer materials and metals. The polymer materials may include, but are not limited to, polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE), while the metals may include, but are not limited to, sodium, copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Composite current collectors can be obtained by blending polymer materials and metals, or by electroplating, coating, or other methods to coat at least one side of the polymer material.
[0126] For negative electrode sheets that include a negative electrode active layer, the negative electrode active material in the negative electrode active layer can be, but is not limited to, a mixture or composite material formed from any one or more of carbon-based materials, alloy materials, titanium-based materials, and sodium metal. Carbon-based materials include, but are not limited to, one or more of graphite, soft carbon, hard carbon, carbon microspheres, and carbon fibers; alloy materials include, but are not limited to, one or more of sodium-tin alloys, sodium-germanium alloys, and sodium-antimony alloys; titanium-based materials include, but are not limited to, one or more of titanium dioxide, titanates, and titanium phosphates.
[0127] The mass content of the negative electrode active material in the negative electrode active layer can be set to 85%~98%, optionally 95%~98%, for example, any one of 85%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or any range between two.
[0128] The negative electrode active layer may also include one or more of conductive agents and binders. Conductive agents are used to collect microcurrents between active materials and between the active materials and the current collector, improving electronic conductivity. Simultaneously, conductive agents can also promote the wetting of the negative electrode sheet by the electrolyte. Binders can improve the bonding strength between the substances in the active layer and between the active layer and the current collector.
[0129] The mass content of the conductive agent in the negative electrode active layer can be set to 0.5%~10%, for example, any one of 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any range between two, or other contents as needed.
[0130] Conductive agents include one or more of acetylene black (SP), carbon nanotubes, conductive carbon black (super-P), Ketjen black, carbon fiber, and graphene.
[0131] The mass content of the binder in the negative electrode active layer is 0.5% to 10%, for example, any one of 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any range between two, or it can be set to other contents as needed.
[0132] The adhesive includes, but is not limited to, one or more of the following: polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyimide, polytetrafluoroethylene, polybutyl acrylate, polyacrylonitrile, carboxymethyl cellulose, carboxymethyl cellulose salt, polyacrylic acid, polyacrylate, polyvinyl alcohol, sodium alginate, cyclodextrin, styrene-butadiene rubber, vinyl acetate resin, acrylic resin, and chlorinated rubber.
[0133] The negative electrode active layer may optionally include a thickener, such as carboxymethyl cellulose (CMC). The mass content of the thickener in the positive electrode active layer can be set to 0.5% to 5%, for example, any one of 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range between any two.
[0134] When the current collector is also the negative electrode active material, the negative electrode sheet can be obtained by cutting the current collector.
[0135] For negative electrode sheets that include a negative electrode active layer, the negative electrode active material can be coated onto at least one side of the current collector using methods such as physical vapor deposition, chemical vapor deposition, or electroplating. Alternatively, the negative electrode sheet can be formed through processes such as slurry preparation, coating, drying, and compaction. For example, a negative electrode active material, a conductive agent, a binder (optionally, other additives may be added as needed), and a solvent are mixed to obtain a negative electrode slurry; the negative electrode slurry is coated onto the current collector, dried, and compacted to obtain the negative electrode sheet. The solvent may include, but is not limited to, N-methylpyrrolidone (NMP). The compaction method may include one or more of hot pressing and cold pressing, and the pressure used in the compaction step can be determined according to the target compaction density.
[0136] 2. Electrolytes The battery also includes an electrolyte solution, with the positive and negative electrodes in independent contact with the electrolyte. The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel-like, or entirely solid.
[0137] Electrolytes can be electrolytes, which include electrolyte salts and solvents.
[0138] Electrolyte salts include one or more of the following: sodium hexafluorophosphate, sodium difluorosulfonamide, sodium trifluoromethanesulfonate, sodium sulfide, sodium chloride, sodium fluoride, sodium sulfate, sodium carbonate, sodium phosphate, sodium nitrate, sodium difluorooxalateborate, sodium pyrophosphate, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, trisodium citrate, sodium metaborate, sodium borate, sodium molybdate, sodium tungstate, sodium bromide, sodium nitrite, sodium iodate, sodium iodide, sodium silicate, sodium lignosulfonate, sodium oxalate, sodium aluminate, sodium methanesulfonate, sodium acetate, sodium dichromate, sodium hexafluoroarsenate, sodium tetrafluoroborate, sodium perchlorate, and sodium trifluoromethanesulfonamide.
[0139] Solvents include ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl ether (DME), diethylene glycol dimethyl ether, diethylene glycol diethyl ether, tetraethylene glycol dimethyl ether, and 2,2,2,2. Trifluoroethyl ether, ethylene glycol diethyl ether, triethylene glycol dimethyl ether, methyl trifluoroethyl carbonate (FEMC), dioxolane (DOL), acetonitrile (AN), fluorobenzene, triethyl phosphate (TEP), sulfolane, 2 One or more of methyltetrahydrofuran, tetrahydrofuran, dimethyl sulfoxide, and N,N-dimethylacetamide.
[0140] Electrolytes may also include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0141] 3. Separating membrane The battery also includes a separator, which is placed between the positive and negative electrodes to separate them. The separator prevents electrons from passing freely within the battery, thus preventing short circuits between the electrodes, but allows ions from the electrolyte to pass freely between the positive and negative electrodes.
[0142] The separator can be any known porous structure separator with electrochemical and mechanical stability, such as one or more single-layer or multi-layer films made of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP) and polyvinylidene fluoride (PVDF).
[0143] 4. Outer packaging The battery may include an outer packaging. This outer packaging may be used to encapsulate an electrode assembly containing a positive electrode, a negative electrode, a separator, and an electrolyte.
[0144] The outer packaging of batteries can be a hard shell, such as a hard plastic shell, aluminum shell, or steel shell; or it can be a soft pack, such as a pouch. The material of the soft pack can be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0145] The outer packaging of the battery can be cylindrical, square, or any other arbitrary shape. For example, Figure 6 This is an example of a battery with a square outer packaging.
[0146] Reference Figure 7 The outer packaging may include a housing 01 and a cover plate 02. The housing 01 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 01 has an opening communicating with the receiving cavity, and the cover plate 02 can be placed over the opening to close the receiving cavity. A positive electrode, a negative electrode, and a separator can be formed into an electrode assembly 03 via a winding or stacking process. One or more electrode assemblies 03 are encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 03.
[0147] 5. Battery cells, battery modules, and battery packs The battery in this application embodiment includes one or more of the following: battery cell, battery module, and battery pack.
[0148] Depending on the packaging, rechargeable batteries are classified into individual cells, battery modules, and battery packs. The individual cell is the most basic unit of a rechargeable battery, comprising electrode assemblies and an electrolyte. Electrode assemblies typically include a positive electrode, a negative electrode, a lithium-ion electrode, and a separator. A bare cell is obtained by alternately stacking positive and negative electrodes, with a separator placed between them for isolation. Alternatively, a bare cell can be obtained by winding the electrodes. The bare cell is then placed in outer packaging, injected with electrolyte, and sealed to obtain the individual battery cell.
[0149] One or more battery cells are integrated to form a battery module, which can provide higher voltage and capacity, and has specific output functions. One or more battery modules are installed in a battery casing, usually with the addition of a battery management system, to form a battery pack. This battery pack is typically a product provided to the user. Alternatively, one or more battery cells can be directly installed in a casing to form a battery pack.
[0150] refer to Figure 8 This is an example battery module. In the battery module, multiple battery cells 04 can be arranged sequentially along the length of the battery module. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 04 can be secured using fasteners.
[0151] Optionally, the battery module may also include a housing with a receiving space in which multiple battery cells 04 are received.
[0152] refer to Figure 9 and Figure 10 This is an example of a battery pack. The battery pack may include a battery compartment and multiple battery modules 05 disposed within the battery compartment. The battery compartment includes an upper housing 06 and a lower housing 07, with the upper housing 06 covering the lower housing 07 to form a closed space for accommodating the battery modules 05. The multiple battery modules 05 can be arranged in any manner within the battery compartment.
[0153] Electrical appliances This application also provides an electrical device, which includes the battery described above.
[0154] The battery disclosed in this application can be used in electrical devices that use batteries as a power source, or in various energy storage systems that use batteries as energy storage elements, to provide electrical energy. The positive electrode of the battery contains a sodium-ion layered oxide positive electrode material with excellent water stability, which can improve the battery's electrochemical performance, such as cycle stability. Therefore, using the battery described above can stably provide electrical energy to various electrical devices, improving the user experience of these devices.
[0155] Electrical devices can include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc. As for the aforementioned electrical devices, battery cells, battery modules, or battery packs can be selected according to their usage requirements.
[0156] Figure 11 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.
[0157] The embodiments of this application are described in detail below. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0158] Ga-doped sodium-ion layered oxide cathode material Example A1 Sodium-ion layered oxide cathode material This embodiment provides a sodium-ion layered oxide cathode material with the chemical formula NaNi. 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Ga 0.01 O2.
[0159] The preparation method of this sodium-ion layered oxide cathode material includes the following steps: (1) Weigh a total of 30g of sample containing Na2CO3, NiO, Fe2O3, Mn2O3, CuO, and Ga2O3 in a molar ratio of Na:Ni:Fe:Mn:Cu:Ga of 1:0.2:0.29:0.4:0.1:0.01. After pre-grinding the sample in an agate mortar, add it to a planetary ball mill and ball mill for 1h to obtain a precursor mixture.
[0160] (2) The obtained precursor mixture was uniformly placed in an open crucible, and then heated from room temperature (25°C) to 950°C in a muffle furnace at a heating rate of 5°C / min. The temperature was then held at 950°C for 15 hours. After natural cooling, the sodium ion layered oxide cathode material NaNi was obtained. 0.2 Fe0.29 Mn 0.4 Cu 0.1 Ga 0.01 O2.
[0161] Sodium-ion batteries The sodium-ion layered oxide cathode material of this embodiment is used as the cathode active material to form a cathode sheet, which is then assembled with a cathode sheet, electrolyte, and separator to form a sodium-ion battery.
[0162] 1) Positive electrode sheet Sodium ion layered oxide cathode material, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and N-methylpyrrolidone (NMP) were mixed evenly at a mass ratio of 60:5:5:30 to obtain a cathode slurry; then, a 20 mg / cm³ solution was prepared. 2 The coating amount is such that the positive electrode slurry is evenly coated onto the positive electrode aluminum foil current collector, and then dried, cold pressed and cut to obtain the positive electrode sheet.
[0163] 2) Negative electrode plate The negative electrode is an active thin sodium metal sheet with a diameter of 16 mm and a thickness of 2 mm.
[0164] 3) Electrolyte In an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed evenly at a volume ratio of 3 / 7. 12.5 wt% NaPF6 sodium salt was added and dissolved in the organic solvent and stirred evenly to obtain the electrolyte.
[0165] 4) Separating membrane Glass fiber with a thickness of 500μm was used as the separator.
[0166] 5) Sodium-ion batteries The positive electrode, separator, and negative electrode are stacked in sequence and wound to form an electrode assembly. The electrode assembly is then placed in a packaging shell, electrolyte is added, and after processes such as encapsulation, formation, and settling, a sodium-ion battery is obtained.
[0167] Example A2 The difference between this embodiment and Embodiment A1 is that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.2 Mn 0.4 Cu 0.05 Ga 0.15 O2; Na2CO3, NiO, Fe2O3, Mn2O3, CuO, and Ga2O3 are weighed according to the molar ratio Na:Ni:Fe:Mn:Cu:Ga of 1:0.2:0.2:0.4:0.05:0.15.
[0168] Example A3 The difference between this embodiment and Embodiment A1 is that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.3 Mn 0.4 Cu 0.09 Ga 0.01 O2; Na2CO3, NiO, Fe2O3, Mn2O3, CuO, and Ga2O3 were weighed according to the molar ratio Na:Ni:Fe:Mn:Cu:Ga of 1:0.2:0.3:0.4:0.09:0.01.
[0169] Example A4 The difference between this embodiment and Embodiment A1 is that Cu is replaced with an equimolar amount of Zn, and the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.29 Mn 0.4 Zn 0.1 Ga 0.01 O2; CuO is replaced with ZnO.
[0170] Example A5 The difference between this embodiment and Embodiment A1 is that Cu is replaced with an equimolar amount of Mg, and the proportions of each element are adjusted so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.30 Mn 0.4 Mg 0.05 Ga 0.05 O2; at the same time, CuO in the raw materials is replaced with MgO.
[0171] Example A6 The difference between this embodiment and embodiment A1 is that the proportion of Ni is reduced, so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.1 Fe 0.39 Mn 0.4 Cu 0.1 Ga 0.01 O2.
[0172] Example A7 The difference between this embodiment and Embodiment A1 is that the sodium ion layered oxide cathode material does not contain Ni, and its chemical formula is NaFe. 0.39 Mn 0.5 Cu 0.1 Ga 0.01 O2.
[0173] Example A8 The difference between this embodiment and Embodiment A1 is that the sodium ion layered oxide cathode material does not contain Cu, and its chemical formula is NaNi. 0.39 Fe 0.2 Mn 0.4 Ga 0.01 O2.
[0174] Example A9 The difference between this embodiment and embodiment A1 is that the proportion of Ni is increased, and the proportions of each element are adaptively adjusted so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.25 Fe 0.39 Mn 0.3 Cu 0.05 Ga 0.01 O2.
[0175] Example A10 The difference between this comparative example and Example A1 is that the proportion of Na is reduced, so that the chemical formula of the sodium ion layered oxide cathode material is Na. 0.7 Ni 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Ga 0.01 O2.
[0176] Comparative Example A1 The difference between this comparative example and Example A1 is that the sodium ion layered oxide cathode material does not contain Ga, and its specific chemical formula is NaNi. 0.2 Fe 0.3 Mn 0.4 Cu 0.1 O2; Na2CO3, NiO, Fe2O3, Mn2O3, and CuO are weighed according to the molar ratio Na:Ni:Fe:Mn:Cu of 1:0.2:0.3:0.4:0.1.
[0177] Comparative Example A2 The difference between this comparative example and Example A1 is that Ga is replaced with an equimolar amount of Al, and the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Al 0.01 O2.
[0178] The chemical formulas of the sodium ion layered oxide cathode materials in Examples A1 to A10, and Comparative Examples A1 and A2 are summarized in the table below.
[0179] Table A1. Chemical formulas of Ga-doped sodium-ion layered oxide cathode materials
[0180] The structures of the sodium-ion layered oxide cathode materials of Examples A1 to A10, as well as Comparative Examples A1 and A2, were tested, including particle size Dv50, specific surface area, tap density, and compaction density. The results are shown in the table below.
[0181] Table A2. Structural test results of Ga-doped sodium ion layered oxide cathode materials
[0182] As can be seen from the table, each sodium ion layered oxide cathode material has a small particle size in the micrometer range and a moderate specific surface area, which will help improve its processing performance. At the same time, each sodium ion layered oxide cathode material also exhibits a large tap density and compaction density, which will help increase the energy density when manufacturing cathode sheets.
[0183] XRD analysis was performed on the sodium-ion layered oxide cathode materials of Examples A1 to A10, as well as Comparative Examples A1 and A2, to obtain the interlayer spacing of the (003) crystal planes in each sodium-ion layered oxide cathode material. l And space group. Meanwhile, after sodium ion layered oxide cathode materials come into contact with water, their interlayer spacing usually changes. Therefore, the water stability of sodium ion layered oxide materials can be represented by the interlayer spacing change rate; the smaller the interlayer spacing change rate, the better the water stability. Each sodium ion layered oxide cathode material was immersed in water for 24 hours, and the interlayer spacing change rate Δ of the (003) crystal plane after immersion was obtained by XRD analysis. l .
[0184] In addition, electrochemical performance tests were conducted on the sodium-ion batteries assembled in each embodiment and comparative example to obtain the specific capacity C0 of the sodium-ion layered oxide cathode material. The relevant performance test results are as follows: Figure 2 , Figure 3 As shown in the table below.
[0185] Table A3. Performance test results of Ga-doped sodium ion layered oxide cathode materials
[0186] in, Figure 2 The X-ray diffraction patterns of undoped Ga sodium-ion layered oxide cathode material (Comparative Example A1) before and after immersion in water are shown. Figure 3The X-ray diffraction (XRD) spectra of the sodium-ion layered oxide cathode material of Example A1, doped with a certain amount of Ga, before and after immersion in water. By comparing the XRD diffraction peaks of the samples with the standard card of the XRD analysis software, it can be confirmed that the phase structure of the sodium-ion layered oxide cathode materials of Comparative Example A1 and Example A1 is O3 phase, with space group R3-m. Figure 2 The results show that after immersion in water for 24 hours, the (003) diffraction peak near 16.5° of the sodium-ion layered oxide cathode materials in Example A1 and Comparative Example A1 shifted compared to before immersion. The shift in the (003) diffraction peak position in Example A1 was significantly smaller than that in Comparative Example A1. This change in diffraction peak position reflects a change in the interlayer spacing. Therefore, the interlayer spacing change in the sodium-ion layered oxide cathode material of Example A1 was smaller after immersion in water for 24 hours, indicating better water stability compared to Comparative Example A1.
[0187] Furthermore, after immersing the sodium-ion layered oxide cathode material in Comparative Example A1 in water for 24 hours, the intensity of its (003) diffraction peak decreased, and its sharp shape changed to a more rounded shape, further indicating that the structure of the sodium-ion layered oxide cathode material in Comparative Example A1 changed after immersion in water, and its crystal structure became unstable. However, after immersion under the same conditions, the intensity of the (003) diffraction peak of the sodium-ion layered oxide cathode material in Example A1 did not decrease, but instead increased, and its sharpness increased, reflecting its good water stability.
[0188] Combining the test data in Table A3, it can be further seen that after the sodium ion layered oxide cathode materials of Examples A1 to A10 were immersed in water for 24 hours, the interlayer spacing Δ of the (003) crystal plane changed. l All were lower than the 1.20% of Comparative Example A1. Meanwhile, in the sodium-ion layered oxide cathode material of Comparative Example A2, due to the replacement of Ga with other elements (Al), the interlayer spacing change rate Δ after immersion in water for 24 hours was significantly lower. l Compared to Examples A1 to A10 and Comparative Example A1, the increase in Ga significantly reduces water stability. Therefore, by doping with appropriate amounts of Ga, the interlayer spacing change of sodium ion layered oxide cathode materials after immersion in water can be effectively reduced, thereby improving the water stability of sodium ion layered oxide cathode materials.
[0189] In addition, the sodium-ion layered oxide cathode materials of each embodiment exhibit high specific capacity, with a smaller decrease in specific capacity compared to undoped Ga, reaching a level comparable to that of common sodium-ion layered oxide cathode materials. This reflects that by doping Ga into sodium-ion layered oxide cathode materials, excellent high specific capacity can be maintained while improving water stability.
[0190] Ta-doped sodium-ion layered oxide cathode material Example B1 The difference between this embodiment and Embodiment A1 is that Ga is replaced with an equimolar amount of Ta, and the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Ta 0.01 O2; Ga2O3 is replaced with Ta2O5.
[0191] Example B2 The difference between this embodiment and embodiment B1 is that the proportions of each element are adjusted so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.2 Mn 0.4 Cu 0.05 Ta 0.15 O2.
[0192] Example B3 The difference between this embodiment and embodiment B1 is that the proportions of each element are adjusted so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.3 Mn 0.4 Cu 0.09 Ta 0.01 O2.
[0193] Example B4 The difference between this embodiment and Embodiment B1 is that Cu is replaced with an equimolar amount of Zn, and the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.29 Mn 0.4 Zn 0.1 Ta 0.01 O2.
[0194] Example B5 The difference between this embodiment and Embodiment B1 is that Cu is replaced with an equimolar amount of Mg, and the balance between the elements is adjusted so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.30 Mn 0.4 Mg 0.05 Ta 0.05 O2.
[0195] Example B6 The difference between this embodiment and Embodiment B1 is that the proportion of Ni element is increased, so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.3 Fe0.19 Mn 0.4 Cu 0.1 Ta 0.01 O2.
[0196] Example B7 The difference between this embodiment and embodiment B1 is that the proportion of Ni element is reduced, so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.1 Fe 0.39 Mn 0.4 Cu 0.1 Ta 0.01 O2.
[0197] Example B8 The difference between this embodiment and Embodiment B1 is that the sodium ion layered oxide cathode material does not contain Ni, and its chemical formula is NaFe. 0.39 Mn 0.5 Cu 0.1 Ta 0.01 O2.
[0198] Example B9 The difference between this embodiment and Embodiment B1 is that the sodium ion layered oxide cathode material does not contain Fe, and Cu is replaced with Zn, while the proportions of each element are adjusted to make its chemical formula NaNi. 0.39 Mn 0.5 Zn 0.1 Ta 0.01 O2.
[0199] Example B10 The difference between this embodiment and Embodiment B1 is that the sodium ion layered oxide cathode material does not contain Mn, and its chemical formula is NaNi. 0.45 Fe 0.5 Cu 0.04 Ta 0.01 O2.
[0200] Example B11 The difference between this embodiment and Embodiment B1 is that the sodium ion layered oxide cathode material does not contain Cu, and its chemical formula is NaNi. 0.39 Fe 0.2 Mn 0.4 Ta 0.01 O2.
[0201] Example B12 The difference between this embodiment and embodiment B1 is that the proportion of Na element is increased, so that the chemical formula of the sodium ion layered oxide cathode material is Na. 1.03 Ni 0.2 Fe 0.29 Mn 0.4 Cu0.1 Ta 0.01 O2.
[0202] Example B13 The difference between this embodiment and embodiment B1 is that the proportion of Na element is reduced, so that the chemical formula of the sodium ion layered oxide cathode material is Na. 0.7 Ni 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Ta 0.01 O2.
[0203] Example B14 The difference between this embodiment and embodiment B1 is that the proportions of each element are adjusted so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.25 Fe 0.39 Mn 0.3 Cu 0.05 Ta 0.01 O2.
[0204] Comparative Example B1 The difference between this comparative example and Example B1 is that the sodium ion layered oxide cathode material does not contain Ta, and its specific chemical formula is NaNi. 0.2 Fe 0.3 Mn 0.4 Cu 0.1 O2.
[0205] Comparative Example B2 The difference between this comparative example and Example B1 is that Ta is replaced with an equimolar amount of Al, and the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Al 0.01 O2.
[0206] The chemical formulas of the sodium ion layered oxide cathode materials in Examples B1 to B14, as well as Comparative Examples B1 and B2, are summarized in the table below.
[0207] Table B1. Chemical formulas of Ta-doped sodium ion layered oxide cathode materials
[0208] The structures of the sodium-ion layered oxide cathode materials of Examples B1 to B14, as well as Comparative Examples B1 and B2, were tested, including particle size Dv50, specific surface area, tap density, and compaction density. The results are shown in the table below.
[0209] Table B2. Structural test results of Ta-doped sodium ion layered oxide cathode materials
[0210] As can be seen from the table, each sodium ion layered oxide cathode material has a small particle size in the micrometer range and a moderate specific surface area, which will help improve its processing performance. At the same time, each sodium ion layered oxide cathode material also exhibits a large tap density and compaction density, which will help increase the energy density when manufacturing cathode sheets.
[0211] XRD tests were performed on the sodium-ion layered oxide cathode materials of Examples B1 to B14, as well as Comparative Examples B1 and B2. The X-ray diffraction patterns of the sodium-ion layered oxide cathode material of Example B1 before and after immersion in water for 24 hours are shown below. Figure 4 As shown. Meanwhile, the sodium-ion layered oxide cathode materials of Examples B1-B14, and Comparative Examples B1 and B2, after being immersed in water for 24 hours, showed the change rate of interlayer spacing Δ of the (003) crystal planes. l The specific capacity C0 is shown in the table below.
[0212] Table B3. Performance test results of Ta-doped sodium ion layered oxide cathode materials
[0213] from Figure 4 As can be seen, similar to Example A1, after the sodium-ion layered oxide cathode material of Example B1 was immersed in water for 24 hours, the position of the (003) diffraction peak near 16.5° shifted significantly compared to before immersion compared to the undoped Comparative Example B1 (i.e., Comparative Example A1). Figure 2 The intensity of the (003) diffraction peak is smaller, and the intensity of the (003) diffraction peak is not weakened, but rather significantly enhanced, with increased sharpness. This indicates that the sodium ion layered oxide cathode material of Example B1 also has better stability than Comparative Example B1, and water immersion has little effect on its structure.
[0214] Meanwhile, the test data in Table B3 also show that after the sodium ion layered oxide cathode materials of Examples B1 to B14 were immersed in water for 24 hours, the interlayer spacing Δ of the (003) crystal plane was reduced. l The content of Ta is only 0.31% to 0.56%, which is far lower than the 1.20% of the undoped comparative example B1 and the comparative example B2 where Ta was replaced with an inappropriate element (Al). Therefore, by doping with appropriate Ta, the interlayer spacing change of sodium ion layered oxide cathode materials after immersion in water can be effectively reduced, thereby improving the water stability of sodium ion layered oxide cathode materials.
[0215] In addition, the sodium-ion layered oxide cathode materials of Examples B1 to B14 exhibited high specific capacity, with a smaller decrease in specific capacity compared to undoped Ta materials. They reached a level comparable to the specific capacity of common sodium-ion layered oxide cathode materials, reflecting that by doping Ta into sodium-ion layered oxide cathode materials, excellent high specific capacity can be maintained while improving water stability.
[0216] Zr-doped sodium-ion layered oxide cathode material Example C1 The difference between this embodiment and Embodiment A1 is that Ga is replaced with an equimolar amount of Zr, and the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Zr 0.01 O2; Ga2O3 is replaced with ZrO2.
[0217] Example C2 The difference between this embodiment and embodiment C1 is that the proportions of each element are adjusted so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.2 Mn 0.4 Cu 0.05 Zr 0.15 O2.
[0218] Example C3 The difference between this embodiment and embodiment C1 is that the proportions of each element are adjusted so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.3 Mn 0.4 Cu 0.09 Zr 0.01 O2.
[0219] Example C4 The difference between this embodiment and embodiment C1 is that Cu is replaced with an equimolar amount of Zn, and the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.29 Mn 0.4 Zn 0.1 Zr 0.01 O2.
[0220] Example C5 The difference between this embodiment and embodiment C1 is that Cu is replaced with an equimolar amount of Mg, and the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.29 Mn0.4 Mg 0.1 Zr 0.01 O2.
[0221] Example C6 The difference between this embodiment and embodiment C1 is that the proportion of Ni element is increased, so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.3 Fe 0.19 Mn 0.4 Cu 0.1 Zr 0.01 O2.
[0222] Example C7 The difference between this embodiment and embodiment C1 is that the proportion of Ni element is reduced, so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.1 Fe 0.39 Mn 0.4 Cu 0.1 Zr 0.01 O2.
[0223] Example C8 The difference between this embodiment and embodiment C1 is that the sodium ion layered oxide cathode material does not contain Ni, and its chemical formula is NaFe. 0.39 Mn 0.5 Cu 0.1 Zr 0.01 O2.
[0224] Example C9 The difference between this embodiment and embodiment C1 is that the sodium ion layered oxide cathode material does not contain Cu, and its chemical formula is NaNi. 0.39 Fe 0.2 Mn 0.4 Zr 0.01 O2.
[0225] Example C10 The difference between this embodiment and embodiment C1 is that the proportions of each element are adjusted so that the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.25 Fe 0.39 Mn 0.3 Cu 0.05 Zr 0.01 O2.
[0226] Example C11 The difference between this embodiment and embodiment C1 is that the sodium ion layered oxide cathode material does not contain Fe, and Cu is replaced with Zn, while the proportions of each element are adjusted so that its chemical formula is NaNi. 0.39 Mn 0.5 Zn0.1 Zr 0.01 O2.
[0227] Example C12 The difference between this embodiment and embodiment C1 is that the proportion of Na element is reduced, so that the chemical formula of the sodium ion layered oxide cathode material is Na. 0.7 Ni 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Zr 0.01 O2.
[0228] Comparative Example C1 The difference between this comparative example and Example C1 is that the sodium ion layered oxide cathode material does not contain Ga, and its specific chemical formula is NaNi. 0.2 Fe 0.3 Mn 0.4 Cu 0.1 O2.
[0229] Comparative Example C2 The difference between this comparative example and Example C1 is that Zr is replaced with an equimolar amount of Al, and the chemical formula of the sodium ion layered oxide cathode material is NaNi. 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Al 0.01 O2.
[0230] The chemical formulas of the sodium ion layered oxide cathode materials in Examples C1 to C12, and Comparative Examples C1 and C2 are summarized in the table below.
[0231] Table C1. Chemical formulas of Zr-doped sodium-ion layered oxide cathode materials
[0232] The structures of the sodium-ion layered oxide cathode materials of Examples C1 to C12, as well as Comparative Examples C1 and C2, were tested, including particle size Dv50, specific surface area, tap density, and compaction density. The results are shown in the table below.
[0233] Table C2. Structural test results of Zr-doped sodium ion layered oxide cathode materials
[0234] As can be seen from the table, each sodium ion layered oxide cathode material has a small particle size in the micrometer range and a moderate specific surface area, which will help improve its processing performance. At the same time, each sodium ion layered oxide cathode material also exhibits a large tap density and compaction density, which will help increase the energy density when manufacturing cathode sheets.
[0235] XRD analysis was performed on the sodium-ion layered oxide cathode materials of Examples C1 to C12, and Comparative Examples C1 and C2 to obtain the interlayer spacing of the (003) crystal planes in each sodium-ion layered oxide cathode material. l And space group. Simultaneously, each sodium ion layered oxide cathode material was immersed in water for 24 hours, and the interlayer spacing change rate Δ of the (003) crystal plane after immersion was obtained by XRD analysis. l In addition, the electrochemical performance of sodium-ion batteries assembled in Examples C1 to C12, as well as Comparative Examples C1 and C2, was tested to obtain the specific capacity of the sodium-ion layered oxide cathode material.
[0236] The performance test results of the sodium-ion layered oxide cathode materials in Examples C1 to C12, and Comparative Examples C1 and C2 are as follows: Figure 5 As shown in the table below.
[0237] Table C3. Performance test results of Zr-doped sodium ion layered oxide cathode materials
[0238] Figure 5 The X-ray diffraction patterns of the sodium-ion layered oxide cathode material of Example C1 before and after immersion in water show that its phase structure is O3 phase and space group is R3-m. Similar to Example A1, the (003) diffraction peak position of the sodium-ion layered oxide cathode material of Example C1 at around 16.5° shows a significant shift compared to before immersion compared to Comparative Example C1 (i.e., Comparative Example A1). Figure 2 The (003) diffraction peak intensity was smaller, and after soaking in water for 24 hours, it did not decrease significantly like that of Comparative Example C1, indicating that the sodium ion layered oxide cathode material of Example C1 has good stability and that water immersion has little effect on its structure.
[0239] Meanwhile, the interlayer spacing change rate Δ in Examples C1 to C12 l It can be as low as 0.10%, exhibiting excellent water stability. In contrast, the interlayer spacing change rate Δ of sodium-ion layered oxide cathode materials after immersion in water for 24 hours is significantly lower when Zr is not doped or when Zr is replaced with Al. lThe relatively large value indicates poor water stability. Therefore, doping sodium ion layered oxide cathode materials with Zr can significantly improve the water stability of the material.
[0240] In addition, the sodium-ion layered oxide cathode materials of Examples C1 to C12 exhibited high specific capacity, with a smaller decrease in specific capacity compared to undoped Zr. They reached a level comparable to the specific capacity of common sodium-ion layered oxide cathode materials, reflecting that by doping elements such as Zr into sodium-ion layered oxide cathode materials, excellent high specific capacity can be maintained while improving water stability.
[0241] Appendix: The specific test methods for the above performance are as follows: (1) Rate of change of interlayer spacing Δ l and space group 1) Grind the sample to be tested in an agate mortar in a drying room or glove box and pass it through a 350-mesh sieve. Take an appropriate amount of the sieved sample and put it into the middle of the groove of the sample holder, so that the loose sample powder is slightly higher than the plane of the sample holder. Take a glass slide and press it lightly on the sample surface to make the sample surface level with the plane of the frame, and scrape off the excess powder.
[0242] After sample preparation, a Brucker D8A-A25 X-ray powder diffractometer from Brucker AxS (Germany) was used to analyze CuK... α The radiation source was X-rays with a wavelength of λ = 1.5406 Å. The scanning angle range was 10° to 70°, and the scanning rate was 4° / min.
[0243] After the test is completed, the angle corresponding to the (003) crystal plane is used, according to Bragg's equation 2. l Given sinθ = λ and the fact that each unit cell of the (003) crystal plane contains three transition metal layers, the interlayer spacing of the (003) crystal plane can be obtained. l The space group of the sample can be confirmed by comparing the XRD diffraction peaks of the sample with the standard card of the XRD analysis software.
[0244] 2) Interlayer spacing variation rate Δ l The sodium ion layered oxide cathode material was obtained by immersion testing. Specifically, 5g of sodium ion layered oxide cathode material was placed in a beaker, 15mL of deionized water was added, and the mixture was stirred vigorously for 1 minute. After standing for 24 hours, the mixture was filtered and vacuum dried at 80℃ for 12 hours to obtain the immersed sodium ion layered oxide cathode material. The changes in the (003) characteristic position in the X-ray diffraction spectrum of the sodium ion layered oxide cathode material before and after immersion in water for 24 hours were observed using the X-ray powder diffractometer described in step 1) above.
[0245] Let θ' represent the position of the (003) characteristic peak in the X-ray diffraction spectrum of the sodium ion layered oxide cathode material after immersion in water for 24 hours, and θ represent the position of the (003) characteristic peak in the X-ray diffraction spectrum of the sodium ion layered oxide cathode material before immersion. According to Bragg's equation 2... l The values before and after soaking in water are calculated using sinθ = λ. l and l Then, the rate of change of interlayer spacing Δ after soaking in water for 24 hours was calculated. l =[( l - l ') / l ] 100%. △ l The smaller the value, the better the material's water stability.
[0246] (2) Specific capacity C0 After preparing a secondary battery from the positive electrode active material at 25℃, it was charged to 4.3V at a constant current density of 10mA / g, and then discharged to 1.5V at a constant current density of 10mA / g to obtain the discharge specific capacity C0 of the secondary battery.
[0247] (3) Dv50 Dv50 was determined using a Malvern 3000 instrument, in accordance with GB / T 19077-2016 / ISO 13320:2009 "Particle size distribution by laser diffraction".
[0248] (4) Specific surface area Referring to GB / T 19587-2017 "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method", the nitrogen adsorption specific surface area analysis method was used, and the result was calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis was performed using a Tri-Star 3020 specific surface area and pore size analyzer from Micromeritics, USA.
[0249] (5) Tap density The tap density was determined using a tap density meter in accordance with GB / T 5162-2021 "Determination of tap density of metal powder".
[0250] (6) Compacted density The density was obtained by using a compaction density meter, referring to Appendix L of GB / T 24533-2019, "Test Method for Powder Compacted Density".
[0251] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A battery, characterized in that, The battery includes a positive electrode sheet, the positive electrode sheet includes a positive active layer, and the positive active layer includes a sodium ion layered oxide positive electrode material, the sodium ion layered oxide positive electrode material including Na... x Ni a Fe b Mn c M 1 d M 2 e O 2-p A p , where 0.6 < x <1.2, 0≤a, 0≤b, 0≤c, 0≤d, 0<e≤0.15, a+b+c+d+e=1, 0<(a+b) / (c+d+e)≤19, 0≤ p ≤0.1; the M 1 Includes one or more elements from groups IA to VA and groups IB to VIIB, wherein M 2 It includes one or more elements selected from Ga, Ta, and Zr, wherein A includes one or more nonmetallic elements from groups VIA and VIIA.
2. The battery according to claim 1, characterized in that, The M 1 It includes one or more of Cu, Li, Ti, K, Nb, Mg, Ca, Mo, Zn, Cr, W, Bi, Sn, Ge, Al, Si, P, and B.
3. The battery according to claim 1 or 2, characterized in that, The A includes one or more of F, Cl, and S.
4. The battery according to any one of claims 1 to 3, characterized in that, 0.01≤e≤0.15, optionally, 0.1≤e≤0.
15.
5. The battery according to any one of claims 1 to 4, characterized in that, 0 < (a+b) / (c+d+e) ≤ 1.8, optionally, 0 < (a+b) / (c+d+e) ≤ 1.
6. The battery according to any one of claims 1 to 5, characterized in that, 0≤a≤0.45, optionally, 0≤a≤0.
4.
7. The battery according to any one of claims 1 to 6, characterized in that, 0 ≤ b ≤ 0.5, optionally, 0.19 ≤ b ≤ 0.
39.
8. The battery according to any one of claims 1 to 7, characterized in that, 0≤c≤0.5。 9. The battery according to any one of claims 1 to 8, characterized in that, 0≤d≤0.2, optionally, 0≤d≤0.
1.
10. The battery according to any one of claims 1 to 9, characterized in that, The M 2 Including Ga, the proportions of each element in the sodium ion layered oxide cathode material are as follows: 0.7≤ x ≤1,0≤a≤0.39,0<b,0<c,0≤d,0<e≤0.15,a+b+c+d+e=1; 0 < (a+b) / (c+d+e) ≤ 1.8; or, The M 2 Including Ta, the proportions of each element in the sodium ion layered oxide cathode material are as follows: 0.6 < x < 1.2, 0 ≤ a, 0 ≤ b, 0 ≤ c ≤ 0.5, 0 ≤ d, 0 < e ≤ 0.15, a+b+c+d+e=1; 0 < (a+b) / (c+d+e) ≤ 19; or, The M 2 Including Zr, the proportions of each element in the sodium ion layered oxide cathode material are as follows: 0.7≤ x ≤1,0≤a≤0.39,0<b,0<c,0≤d,0<e≤0.15,a+b+c+d+e=1;0<(a+b) / (c+d+e)≤1.8。 11. The battery according to any one of claims 1 to 10, characterized in that, The above-mentioned cylindrical material contains NaNi 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Ga 0.01 O2, NaNi 0.2 Fe 0.2 Mn 0.4 Cu 0.05 Ga 0.15 O2, NaNi 0.2 Fe 0.3 Mn 0.4 Cu 0.09 Ga 0.01 O2, NaNi 0.2 Fe 0.29 Mn 0.4 Zn 0.1 Ga 0.01 O2, NaNi 0.2 Fe 0.3 0Mn 0.4 Mg 0.05 Ga 0.0 5O2, NaNi 0.1 Fe 0.39 Mn 0.4 Cu 0.1 Ga 0.01 O2, NaFe 0.39 Mn 0.5 Cu 0.1 Ga 0.01 O2, NaNi 0.39 Fe 0.2 Mn 0.4 Ga 0.01 O2, NaNi 0.25 Fe 0.39 Mn 0.3 Cu 0.05 Ga 0.01 O2, Na 0.7 Ni 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Ga 0.01 O2, NaNi 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Ta 0.01 O2, NaNi 0.2 Fe 0.2 Mn 0.4 Cu 0.05 Ta 0.15 O2, NaNi 0.3 Fe 0.3 Mn 0.4 Cu 0.09 Dad 0.01 O2、NaNi 0.2 Feb 0.29 Mr 0.4 Zn 0.1 Dad 0.01 O2、NaNi 0.2 Feb 0.30 Mr 0.4 Mg 0.05 Dad 0.0 5O2、NaNi 0.3 Feb 0.19 Mr 0.4 Cu 0.1 Dad 0.01 O2、NaNi 0.1 Feb 0.39 Mr 0.4 Cu 0.1 Dad 0.01 O2、NaFe 0.39 Mr 0.5 Cu 0.1 Dad 0.01 O2、NaNi 0.39 Mr 0.5 Zn 0.1 Dad 0.01 O2、NaNi 0.45 Feb 0.5 Cu 0.04 Dad 0.01 O2、NaNi 0.39 Feb 0.2 Mr 0.4 Dad 0.01 O2、Na 1.03 Ni 0.2 Feb 0.29 Mr 0.4 Cu 0.1 Dad 0.01 O2、Na 0.7 Ni 0.2 Feb 0.29 Mr 0.4 Cu 0.1 Dad 0.01 O2、NaNi 0.25 Feb 0.39 Mr 0.3 Cu 0.05 Dad 0.01 O2、NaNi 0.2 Feb 0.29 Mr 0.4 Cu 0.1 Zr 0.01 O2、NaNi 0.2 Feb 0.2 Mn 0.4 Cu 0.05 Zr 0.15 O2, NaNi 0.2 Fe 0.3 Mn 0.4 Cu 0.09 Zr 0.01 O2, NaNi 0.2 Fe 0.29 Mn 0.4 Zn 0.1 Zr 0.01 O2, NaNi 0.2 Fe 0.29 Mn 0.4 Mg 0.1 Zr 0.01 O2, NaNi 0.3 Fe 0.19 Mn 0.4 Cu 0.1 Zr 0.01 O2, NaNi 0.1 Fe 0.39 Mn 0.4 Cu 0.1 Zr 0.01 O2, NaFe 0.39 Mn 0.5 Cu 0.1 Zr 0.01 O2, NaNi 0.39 Fe 0.2 Mn 0.4 Zr 0.01 O2, NaNi 0.2 5Fe 0.39 Mn 0.3 Cu 0.05 Zr 0.01 O2, NaNi 0.39 Mn 0.5 Zn 0.1 Zr 0.01 O2, Na 0.7 Ni 0.2 Fe 0.29 Mn 0.4 Cu 0.1 Zr 0.01 One or more kinds of O2 medium.
12. The battery according to any one of claims 1 to 11, characterized in that, The phase structure of the sodium ion layered oxide cathode material includes one or more of the following: O3 phase, O2 phase, P2 phase, and P3 phase; optionally, the space group of the sodium ion layered oxide cathode material includes R3-m. P 63 / mmc One or more of them.
13. The battery according to any one of claims 1 to 12, characterized in that, The interlayer spacing of the sodium ion layered oxide cathode material is 0.4 nm to 0.6 nm, and optionally 0.5 nm to 0.6 nm.
14. The battery according to any one of claims 1 to 13, characterized in that, The Dv50 of the sodium ion layered oxide cathode material is 10 μm to 30 μm, and optionally 10 μm to 20 μm.
15. The battery according to any one of claims 1 to 14, characterized in that, The specific surface area of the sodium ion layered oxide cathode material is 0.1 m². 2 / g~5m 2 / g, optionally 0.3m 2 / g~3m 2 / g.
16. The battery according to any one of claims 1 to 15, characterized in that, The tap density of the sodium ion layered oxide cathode material is 1 g / cm³. 3 ~3g / cm 3 Optionally, it can be 1.5 g / cm³. 3 ~2.5g / cm 3 .
17. The battery according to any one of claims 1 to 16, characterized in that, The sodium ion layered oxide cathode material has a powder compaction density of 3 g / cm³ under 8 tons of pressure. 3 ~5g / cm 3 Optionally, it can be 3.5g / cm³. 3 ~4.5g / cm 3 .
18. The battery according to any one of claims 1 to 17, characterized in that, The positive electrode active layer further includes a sodium supplementation additive, which includes one or more of transition metal sodium salts, sodium azide, sodium squaric acid salts, and Prussian blue sodium salts; and / or, the mass content of the sodium supplementation additive in the positive electrode active layer is 0.1% to 20%.
19. An electrical appliance, characterized in that, The electrical device includes the battery described in any one of claims 1 to 18.